laminated sheet
Patent Information
- Application Number
- KR1020227015124
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-18
- Filing Date
- 2020-11-11
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2040-11-11
Smart Images

Figure 112022047701119-PCT00010_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a laminated sheet with excellent electromagnetic shielding properties. Background Technology
[0002] With the advancement of communication technology, meter waves in the hundreds of MHz to several GHz band are primarily used in mobile phones and wireless communications; centimeter waves in the several GHz to tens of GHz band are primarily used in mobile communications such as 4G and 5G and wireless LAN (Wi-Fi) communications; and millimeter waves in the tens of GHz to hundreds of GHz band are primarily used in applications such as automotive collision avoidance radar. As such, electromagnetic waves of various frequency bands are scattered throughout the atmosphere. Although the appropriate frequency band for electromagnetic waves is selected based on information capacity, transmission distance, and application, concerns regarding device malfunction, communication interference, and information leakage arise because electromagnetic waves in nearby frequency bands are used in various devices and applications. Furthermore, the impact on the human body, which is sensitive to electromagnetic waves, has also been pointed out. In response to these concerns and criticisms, the demand for electromagnetic shielding materials that shield against electromagnetic waves is increasing. In particular, in recent years, in order to realize high-speed and high-capacity communication, the development of communication technology using electromagnetic waves in the GHz frequency band has been accelerated, and there is a demand for electromagnetic shielding materials that can shield electromagnetic waves in the said frequency band.
[0003] Electromagnetic waves propagate through space as waves composed of two components, an electric field and a magnetic field. Electromagnetic shielding materials that shield electromagnetic waves refer to materials that lose or attenuate the energy of electromagnetic waves by reflecting them from the surface or interior of the material, or by absorbing them from within the material, and the effect can be enhanced by combining reflection and absorption. For example, conductive reflection technology based on reflection from the surface of a material can be enhanced by having different electrical resistance values (impedance calculated based on the relative permittivity) between the air interface and the interface of the electromagnetic shielding material, and generally, electromagnetic shielding properties are obtained over a wide frequency band by coating and laminating a material with a very low resistance value, such as a metal (copper), on the surface of a substrate (Patent Document 1). Meanwhile, electromagnetic wave absorption technology by absorption within a material involves incorporating conductive and / or magnetic materials within the material to convert electromagnetic waves entering the interior into induced currents, thereby causing energy loss of the electromagnetic waves. Absorption performance is achieved by incorporating metal materials, such as carbon materials or ferrites, into dielectric polymers such as rubber (Patent Documents 2 to 4). Additionally, by overlapping layers with different impedances, electromagnetic waves reflected from the front and back of the electromagnetic shield material can be interfered with and canceled out to cause loss (Patent Document 5).
[0004] In particular, electromagnetic shielding properties due to absorption vary depending on the combination of a dielectric (insulating) substrate and a conductive material contained within, the thickness of the substrate, and the formulation of the conductive material (type of material, combination method, content). However, the arrangement state of the conductive material within the substrate is also an important factor, and there is a view called the Maxwell-Wagner effect, which can enhance the overall effect of the shielding material by arranging the conductive material in a certain direction and overlapping it in a transverse arrangement to improve conductivity (Non-patent Literature 1). Prior art literature
[0005] Japanese Patent Publication No. 2011-502285 Japanese Patent Publication No. 2003-158395 Japanese Patent Publication No. 2017-118073 Japanese Patent Publication No. 2019-057730 Japanese Patent Publication No. 2019-102665
[0006] ZM Dang, Prog. Matter. Sci., 2012, 57, 660-723 The problem to be solved
[0007] Regarding electromagnetic shielding materials utilizing conductive reflection technology as described in Patent Document 1, techniques such as metal sputtering, vacuum deposition, or coating a paste material containing conductive and / or magnetic materials on the outermost surface are used; however, there are cases where short circuits in electronic and communication devices occur due to peeling, or problems arise in terms of durability. On the other hand, regarding electromagnetic shielding materials utilizing magnetic absorption or dielectric absorption as described in Patent Documents 2 to 5, in existing technology in which a substrate contains a conductive material, it was necessary to make the substrate thicker or increase the content of the conductive material in order to increase the absolute value of the electromagnetic attenuation amount (increase electromagnetic shielding performance). That is, once the material to be used is determined, electromagnetic shielding performance is required in proportion to the product of the amount of conductive material contained per unit volume of the substrate and the thickness of the substrate (this relationship is referred to as the "volume law"). However, if the thickness of the substrate is increased, the elasticity of the electromagnetic shielding material becomes stronger, making it difficult to apply to uses requiring moldability, such as winding into cables or assembling the shielding material along housings with complex uneven shapes.
[0008] Meanwhile, considering the moldability and production efficiency of the shield material, continuous sheet formation by melt extrusion using thermoplastic resin is preferable to press-formed products using thermoplastic resin; however, when forming a sheet containing a high concentration of conductive material, the thickening effect (thixotropic properties) of the resin composition during extrusion becomes strong, leading to problems such as non-uniformity of discharge during sheet extrusion, making it difficult to form a sheet of uniform thickness, or the sheet becoming brittle and prone to cracking. means of solving the problem
[0009] To solve the above problem, the present invention is composed of the following components. That is,
[0010] A laminated sheet comprising an alternating laminated unit in which two layers with different conductivity, for convenience, the layer with lower conductivity is referred to as layer A and the layer with higher conductivity is referred to as layer B, are alternately laminated in a total of five or more layers, wherein, for the laminated sheet, when a frequency-reflection attenuation curve is obtained with the vertical axis as attenuation and the horizontal axis as frequency, the reflection attenuation at the peak top of the reflection attenuation peak with the largest reflection attenuation is 5 dB or more. Effects of the invention
[0011] The laminated sheet of the present invention exhibits high electromagnetic shielding properties. Therefore, it can be suitably used as an electromagnetic shielding material. In a more preferred embodiment, by forming a laminated structure in which a layer of high conductivity and a layer of low conductivity are alternately laminated, it has steeply high electromagnetic shielding properties for a specific frequency band. Furthermore, even with a low content of conductive material and even as a thin film, it is possible to obtain electromagnetic shielding properties at a level equivalent to that of conventional technology. Therefore, improvements in molding conformability for applied products and stable production of the sheet can be expected. Brief explanation of the drawing
[0012] FIG. 1 is a schematic diagram illustrating the half-width of the reflection attenuation peak, where the reflection attenuation at the peak top is the largest, and the reflection attenuation at the peak top, in a frequency-reflection attenuation curve of a laminated sheet, which is one embodiment of the present invention. Figure 2 is a schematic diagram illustrating the frequency-reflection attenuation curve of a laminated sheet of a different form from Figure 1, the half-width of the reflection attenuation peak with the largest reflection attenuation at the peak top, and the reflection attenuation at the peak top. Figure 3 is a schematic diagram illustrating the half-width of the reflection attenuation peak, where the reflection attenuation at the peak is the largest, and the reflection attenuation at the peak, in a frequency-reflection attenuation curve of a laminated sheet having a different aspect from Figures 1 and 2. FIG. 4 is a schematic diagram illustrating the half-width of the reflection attenuation peak, where the reflection attenuation at the peak is the largest, and the reflection attenuation at the peak, in a frequency-reflection attenuation curve of a laminated sheet having a different aspect from FIG. 1 to 3. Specific details for implementing the invention
[0013] Hereinafter, the laminated sheet of the present invention will be described in detail.
[0014] The laminated sheet of the present invention is a laminated sheet comprising an alternating laminated unit in which layers A and B with different conductivity are alternately laminated in a total of five or more layers. For the laminated sheet, when a frequency-reflection attenuation curve is obtained with the vertical axis representing reflection attenuation and the horizontal axis representing frequency, it is necessary that the reflection attenuation amount (reflection attenuation amount RL) at the peak top of the reflection attenuation peak with the largest reflection attenuation amount at the peak top is 5 dB or more. In addition, the frequency-reflection attenuation curve is obtained by the measurement method described below.
[0015] The laminated sheet of the present invention comprises different layers, referred to as Layer A and Layer B, which have different conductivity. The materials constituting Layer A and Layer B are not particularly limited, such as transparent / opaque, flexible / rigid, flat / non-flat, organic (polymer) material / inorganic (metal) material, etc., but considering processability, it is preferable that the substrate be made of an organic polymer material exhibiting flexibility. In particular, it is preferable that the main component be a thermoplastic resin. Here, "main component" means that the layer is composed solely of a thermoplastic resin, or that other materials, such as conductive materials or magnetic materials, are dispersed within the resin using a thermoplastic resin as the matrix resin.
[0016] In addition, the laminated sheet of the present invention may use a hard coat using a thermosetting resin or a photocurable resin.
[0017] In the laminated sheet of the present invention, layer A and layer B must be layers with different conductivity. Furthermore, for convenience and considering the preferred embodiment of the laminated sheet described below, the layer with lower conductivity is referred to as layer A, and the layer with higher conductivity is referred to as layer B. Different conductivity between layer A and layer B indicates that the surface resistance values, which are indicators of conductivity / insulation in the layer direction (planar direction of the sheet), of each layer A and layer B are different. Specifically, different conductivity between layer A and layer B indicates that, when the higher surface resistance value among the surface resistance values of layer A and layer B is denoted as α [Ω / □] and the lower surface resistance value as β [Ω / □], α / β is 1.1 or higher. Preferably, α / β is 10 2 Above, more preferably 10 5 The above, more preferably 10 9 That is all. The surface resistance value, an indicator of conductivity / insulation, is 1.0 × 10⁻⁶ 5 Since electromagnetic shielding properties are well exhibited when [Ω / □] is less than, the surface resistance of layer A is 1.0×10 5[Ω / □] or higher, and the surface resistance of layer B is 1.0×10 5 It is more preferable to have a ratio of the surface resistance values that is less than [Ω / □]. The method of making the conductivity of layer A and layer B different is not particularly limited. As a material design to make the conductivity of layer A and layer B different, layer A and layer B can be simply composed of a composition containing a conductive material in a matrix, but the conductivity may be different by using a material with a different relative permittivity as the matrix material, or by changing the type and / or content of the conductive material contained therein. Although details will be described later, in order to obtain a high amount of electromagnetic wave attenuation in a specific frequency band, it is important to control the value of the relative permittivity to a specific numerical range. In order to adjust the frequency of the reflection attenuation peak in the target frequency band while maintaining the amount of electromagnetic wave attenuation, a configuration that allows for fine adjustment of the conductivity of layer A and layer B is desirable, and in order to make the relative permittivity of layer A and layer B different, an embodiment in which a conductive material and / or a magnetic material is contained in layer A and / or layer B is most desirable. The relative permittivity described here refers to a dimensionless quantity representing the magnitude of permittivity when based on the permittivity (electric constant) in vacuum. Hereinafter, relative permittivity will be simply referred to as permittivity.
[0018] In addition, the surface resistance value refers to the resistance value of the sample obtained from the surface of the sample. Although it can be obtained by peeling off the interface where layers A and B are stacked to expose the interface, it is easier to obtain and more reproducibly obtain it by slicing each layer to expose the surface of the sample and measuring.
[0019] In the laminated sheet of the present invention, in order to exhibit a high value for the attenuation of the reflection attenuation peak, which has the largest attenuation at the peak top, it is important to design the layer exhibiting a high dielectric constant among the A layer and B layer constituting the alternating laminated unit. Typically, in the technology of conventional single-film sheets, this is often achieved by containing a high concentration of conductive material and / or magnetic material to increase the dielectric constant in the resin, or by increasing the sheet thickness. However, in the laminated sheet of the present invention, by making the dielectric constant of one layer high and the dielectric constant of the other layer low to create a difference in dielectric constant, the effect of dielectric polarization (generation of dipole moment) occurring at the layer interface between the layer with high dielectric constant and the layer with low dielectric constant is applied. Consequently, compared to a single-film sheet containing conductive material and / or magnetic material of the same weight concentration, an effect of dielectric constant improvement greater than the volume law can be obtained. To strongly induce the dielectric polarization that contributes to this dielectric constant improvement, one of the important design points is how to make the difference in dielectric constant between the alternating A layer and B layer large. As described above, methods for varying the dielectric constant include the type of resin used in layers A and B, and differences in the content of conductive materials and / or magnetic materials contained in layers A and / or B. However, a preferred embodiment is one in which only one layer, either layer A or layer B, contains a conductive material, while the resin on the other side consists of a single resin that does not contain a conductive material. A more preferred embodiment is one in which the layer that does not contain a conductive material is composed of a resin with a low dielectric constant, and the layer containing a conductive material is composed of a resin that exhibits a high dielectric constant while also containing a high concentration of conductive material. Furthermore, as described below, increasing the number of layers is desirable because it increases the number of interfaces that cause dielectric polarization, and reducing the thickness of the layers is also desirable because it can increase the number of interfaces per unit thickness.That is, regarding the number of interfaces between layer A and layer B per unit thickness of the alternating laminated unit, it is preferable to have 2 interfaces / 100㎛ or more, more preferable to have 5 interfaces / 100㎛ or more, and even more preferable to have 10 interfaces / 100㎛ or more. As long as the manufacturing of the laminate can be achieved stably, there is no particular upper limit, but it is generally 150 interfaces / 100㎛ or less in terms of productivity. Also, at this time, the ratio of the surface resistance values of layer A and layer B (layer A / layer B) is 1×10. 10 Ideally, 1×10 12 It is better to do it this way.
[0020] As an organic polymer material exhibiting flexibility that can be preferably used in the present invention, it is preferred to be a thermoplastic resin, as this is particularly advantageous in terms of sheet processability and film formation properties.As thermoplastic resins, for example, polyolefin resins represented by polyethylene, polypropylene, poly(1-butene), poly(4-methylpentene), polyisobutylene, polyisoprene, polybutadiene, polyvinylcyclohexane, polystyrene, poly(α-methylstyrene), poly(p-methylstyrene), polynorbornene, polycyclopentene, etc., polyamide resins represented by nylon 6, nylon 11, nylon 12, nylon 66, etc., ethylene / propylene copolymer, ethylene / vinylcyclohexane copolymer, ethylene / vinylcyclohexene copolymer, ethylene / alkyl acrylate copolymer, ethylene / acryl methacrylate copolymer, ethylene / norbornene copolymer, ethylene / vinyl acetate copolymer, propylene / butadiene copolymer, isobutylene / isoprene copolymer, Vinyl monomer copolymer resins represented by vinyl monomer copolymers such as vinyl chloride / vinyl acetate copolymer, acrylic resins represented by polyacrylates, polymethacrylates, polymethyl methacrylates, polyacrylamide, polyacrylonitrile, etc., polyester resins represented by polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, etc., polyether resins represented by polyethylene oxide, polypropylene oxide, polyacrylene glycol, cellulose ester resins represented by diacetylcellulose, triacetylcellulose, propionylcellulose, butyrylcellulose, acetylpropionylcellulose, nitrocellulose, biodegradable polymers represented by polylactic acid, polybutylsuccinate, etc., other polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, Polyvinyl butyral, polyacetal, polyglycolic acid, polycarbonate, polyketone, polyethersulfone, polyetheretherketone, modified polyphenylene ether, polyphenylene sulfide, polyetherimide, polyimide, polysiloxane, tetrafluoroethylene resin, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, etc. may be used.These thermoplastic resins may be used as a single type or as a polymer blend or polymer alloy of two or more types. By forming a blend or alloy, heat resistance, viscosity characteristics, and adhesion at the interlayer interface, which cannot be obtained from a single type of thermoplastic resin, can be obtained.
[0021] As described above, in the laminated sheet of the present invention, by making it a laminated sheet comprising an alternating laminated unit in which layers with different conductivity are alternately laminated, dielectric polarization is induced at the interface between layer A and layer B with different conductivity, thereby obtaining the effect of increasing electromagnetic shielding performance; therefore, the dielectric constant of the thermoplastic resin constituting each layer is an important factor. For this reason, it is desirable that the resin constituting layer A and the resin constituting layer B have different dielectric constants. Specifically, as a resin with a low dielectric constant, it is desirable to select a resin that exhibits a dielectric constant of 3.0 or less. Considering general utility, processability, and lamination properties, it is desirable to select from thermoplastic resins such as polyolefin resin (dielectric constant: 2.0 to 2.3), polyester resin (dielectric constant: 2.8 to 3.0), polycarbonate (dielectric constant: 2.9 to 3.0), and polystyrene (dielectric constant: 2.4 to 2.6). These resins are more preferably used in layers that do not contain conductive materials.
[0022] Meanwhile, as a thermoplastic resin that can be preferably used in a layer containing a conductive material, it is preferable that it has a high dielectric constant, and it is preferable to select from acrylic resin (dielectric constant: 3.0 to 4.5), nylon resin (dielectric constant: 3.5 to 5.0), cellulose-based resin (dielectric constant: 6.7 to 8.0), vinyl monomer copolymer-based resin (dielectric constant: 3.0 to 8.0), fluoropolymer (dielectric constant: 4.0 to 8.0), polyphenylene sulfide (dielectric constant: 3.5 to 4.0), etc.
[0023] In addition, the method of making the dielectric constants of Layer A and Layer B different can be achieved by using materials with different dielectric constants as resins, but it can also be achieved by using the same resin constituting Layer A and Layer B and adding a conductive material to impart conductivity to create a difference in dielectric constant. The laminated sheet of the present invention is characterized by the ability to enhance electromagnetic shielding performance through dielectric polarization occurring at the layer interface by alternately laminating Layer A and Layer B with different conductivity as described above and below, and creating a difference in dielectric constant between Layer A and Layer B. To enhance the effect of dielectric polarization, it is more effective when the difference in dielectric constant between Layer A and Layer B is larger, while to increase the amount of reflection attenuation, it is preferable that the layer with the higher dielectric constant (Layer B) be designed within a specific dielectric constant range described below, and it is desirable to have a configuration that is easy to design the material to match the target dielectric constant. Since fine adjustment of the dielectric constant is easier to achieve by adjusting the content of the added conductive material rather than the resin constituting the layer, a preferred embodiment of a laminated sheet satisfying these conditions is preferably one in which the layer with the lower dielectric constant (layer A) is composed of a layer that does not contain a conductive material, and the layer with the higher dielectric constant (layer B) is composed of a layer that contains a conductive material. More preferably, the embodiment is one in which the resin constituting layer A is composed of a resin exhibiting a dielectric constant of 3.0 or less, and the resin constituting layer B is composed of a resin exhibiting a dielectric constant of 3.0 or more, thereby containing a conductive material.
[0024] The laminated sheet of the present invention requires that it include an alternating laminated unit in which A layer and B layer are alternately laminated five or more times. Alternating lamination refers to a state in which, in the case of a configuration having A layer as the outermost layer, the layers are laminated according to a regular arrangement of A(BA)n or A(BA)nB (where n is an integer greater than or equal to 2). For example, a laminated sheet having a configuration of A layer / B layer / A layer / B layer / A layer, or a configuration of B layer / A layer / B layer / A layer / B layer, corresponds to a configuration that includes an alternating laminated unit in which A layer and B layer are alternately laminated a total of five or more times, regardless of whether there are layers other than A layer and B layer. As long as the laminated sheet of the present invention has an alternating laminated unit in which A layer and B layer are laminated, the outermost layer may be any of A layer, B layer, or layers other than A layer and B layer, and the outermost layers on both sides may be the same layer or different layers. In addition, the number of alternating stacking units included in the laminated sheet may be one or multiple, and in the case of multiple, each alternating stacking unit may have the same configuration or be an alternating stacking unit with a different configuration. When using multiple alternating stacking units, it is easy to realize electromagnetic shielding corresponding to multiple wavelength regions. That is, when using multiple alternating stacking units in a superposition manner, it is easy to simultaneously shield multiple desired frequency bands by superimposing alternating stacking units having peak tops in different frequency bands.
[0025] As a method for alternately laminating elastomer resins such as rubber, for example, a method of producing sheets by rolling and pressing two types of elastomer resins composed of different compositions, and obtaining laminated sheets by alternately overlapping and heat-pressing the other sheets.
[0026] Meanwhile, as a method for alternately laminating thermoplastic resins, for example, a master pellet is prepared by distributing / dispersing and mixing the thermoplastic resin corresponding to each layer and an appropriate additive, and the master pellet is sent from different flow paths using two or more extruders, and laminated using a known lamination device such as a multi-manifold type feed block or a static mixer. In particular, as described below, since the laminated sheet of the present invention is desirable for exhibiting high electromagnetic wave attenuation performance for a specific frequency when the variation in layer thickness is small and the thickness is aligned, it is preferable to form the laminated sheet using a feed block having a fine slit to realize high-precision lamination. Furthermore, by using a slit-type feed block, conductive materials and / or magnetic materials are oriented and dispersed according to the laminar flow of the resin, making it easier to realize a high dielectric constant of the laminated sheet. When forming a laminate using a slit-type feed block, the thickness and distribution of each layer can be achieved by adjusting the pressure balance by changing the length or width of the slit. In addition, the length of the slit here refers to the length of the comb section that forms a flow path for alternately flowing layer A and layer B within the slit plate.
[0027] When manufacturing a laminated sheet using the latter thermoplastic resin, it is desirable that the melt viscosities of the two different types of thermoplastic resins (conveniently referred to as Resin A and Resin B, respectively) be at the same level. If the melt viscosities differ significantly, lamination misalignment (flow marks) of the resins at the lamination interface may occur, making it impossible to produce a uniform sheet. Consequently, the layer thickness of each layer and the accompanying conductivity of each layer become non-uniform, which may cause the electromagnetic shielding performance to fluctuate depending on the position within the laminated sheet. To form a uniform laminated sheet by melt extrusion, a constant temperature (the melting point of the resin with the higher melting point between Resin A and Resin B + 10°C) and a constant shear rate (100 sec) must be applied to either Resin A or Resin B. -1In the case where the melt viscosity of the resin with the higher melt viscosity is denoted as X [poise] and the melt viscosity of the resin with the lower melt viscosity is denoted as Y [poise], it is preferable that the ratio of these (X / Y) be 1.0 ≤ X / Y ≤ 5.0, and more preferably 1.0 ≤ X / Y ≤ 2.0. Furthermore, when a conductive material is incorporated as a filler into a thermoplastic resin, the high concentration of the filler causes a change in melt viscosity dependent on the shear rate (thixotropic properties), making it more likely for flow marks to occur strongly during the resin lamination process. Additionally, even with thermoplastic resins alone, depending on the type such as olefin resins, shear dependence of the resin's melt viscosity occurs, making it easy for flow marks to occur during lamination; furthermore, combining a resin prone to thixotropic properties with a filler results in even stronger flow marks. Therefore, as a thermoplastic resin, it is desirable to use a resin that is difficult to generate thixotropy. Specifically, considering the blendability of the conductive material, it is desirable to select from olefin-based copolymer resins, nylon resins, polyester resins, etc. Alternatively, to match the shear dependence of the melt viscosity with the addition of the conductive material in the layer exhibiting high conductivity, it is also effective to suppress flow marks in the laminated sheet by using a resin material that exhibits non-Newtonian properties, such as olefins, by adding particles different from the conductive material to the layer with low conductivity that does not contain the conductive material, or by using a resin material that exhibits non-Newtonian properties.
[0028] The number of layers in the laminated sheet of the present invention must be five or more. In order to obtain many interfaces where dielectric polarization occurs in any of the above regular arrangements, it is necessary to have a composition of five or more layers so that two or more layers of high dielectric constant surrounded by layers of low dielectric constant are included. Compared to conventional single-layer or low-layer products, where the desired electromagnetic shielding properties could not be achieved without adding a high concentration of conductive material or increasing the thickness of the sheet, by alternately laminating five or more layers, it becomes easier to obtain the effect of dielectric polarization at the interfaces of layers with different conductivity. That is, due to dielectric polarization, current becomes easier to pass through the interior of the sheet (especially in the region near the layer interface), and the energy of the electromagnetic waves is lost due to the resistance of the conductive material, thereby obtaining an electromagnetic shielding material with high shielding properties. In addition, increasing the number of layers in a laminated sheet of a constant thickness reduces the thickness per layer of the laminated sheet, making it easier for conductive materials and / or magnetic materials to be dispersed and arranged in a direction parallel to the surface. Consequently, the conductivity and dielectric constant of the laminated sheet tend to increase, and equivalent effects can be obtained at a low concentration, whereas in a single-layer product, conductive materials and / or magnetic materials could not be achieved without containing them at a high concentration. The sum of the number of layers of A and B in the alternating laminated unit included in the laminated sheet is preferably 11 layers or more, more preferably 31 layers or more, and even more preferably 101 layers or more. A higher number of layers is preferable because, in addition to the above effects, for a laminated sheet of the same thickness, increasing the number of layers increases the packing density of the conductive materials within the layers, thereby narrowing the distance between the conductive materials and increasing the electron transfer efficiency between the added conductive materials, which enhances the effect as an electromagnetic wave absorbing material. In addition, as the number of layers increases and the thickness of each layer decreases, the number of layers included per unit thickness increases, which increases the effect of dielectric polarization and further increases the dielectric constant of the laminated sheet.Although there is no specific upper limit on the number of layers in a laminated sheet, if a feed block with fine slits is used, increasing the number of layers leads to an increase in manufacturing costs as the device becomes larger. Furthermore, depending on the dispersion state, shape, and size of the filler, if the number of layers increases and the thickness of each layer becomes thinner, thixotropic properties caused by particle addition are prone to occur. This causes the resins to become disordered and the layer thickness to fluctuate significantly, which may compromise the inherent high shielding and sharp electromagnetic shielding properties. Therefore, realistically, the upper limit for the number of layers is 2,000 layers or less.
[0029] The laminated sheet of the present invention may include, in addition to an alternating laminated unit in which layers A and B with different conductivity are alternately laminated five or more times, layers with other functions such as electromagnetic wave reflecting layers or electromagnetic wave absorbing layers.
[0030] The laminated sheet of the present invention is preferably an electromagnetic wave absorbing sheet containing a conductive material and / or a magnetic material, but it may also be a laminated sheet capable of shielding only specific frequencies more strongly while shielding electromagnetic waves broadly by combining an electromagnetic wave reflecting layer that shields a wide frequency band, or a laminated sheet with an enhanced electromagnetic wave absorption effect by providing a new layer having a low dielectric constant to further reduce the reflection of electromagnetic waves from the surface on the outermost surface of the laminated sheet. In the latter case, the dielectric constant of the layer located on the outermost surface of the laminated sheet is preferably 4.0 or less, and more preferably 3.0 or less. In addition, as a layer that suppresses surface reflection, it is also desirable to provide a resistive layer having an impedance equal to the impedance of the air layer. The impedance of air is 377Ω, and ITO, etc., can be cited as a known resistive layer that satisfies this resistance value.
[0031] The laminated sheet of the present invention requires that when a frequency-reflection attenuation curve is obtained with the vertical axis representing the reflection attenuation and the horizontal axis representing the frequency, the reflection attenuation at the peak top of the reflection attenuation peak, which has the largest attenuation at the peak top, is 5.0 dB or more. The reflection attenuation is calculated by irradiating an electromagnetic wave onto a laminated sheet, placing a detector on the side of the side of the electromagnetic wave irradiation, and placing a material that totally reflects the electromagnetic wave to the side of the incident side on the side opposite to the side of the electromagnetic wave irradiation, measuring the intensity of the electromagnetic wave returning from the laminated sheet, and based on the relationship between the reflection attenuation Γ represented by Equation (1) and the ratio of the intensity of the returned electromagnetic wave to the intensity of the incident electromagnetic wave (T[%]), from the intensity of the incident electromagnetic wave and the intensity of the electromagnetic wave detected by the detector, and the reflection attenuation Γ is expressed in units of decibels (dB). In addition, the measurement of reflection attenuation or the determination of peak peaks is obtained by the method described in "Measurement of Reflection Attenuation" below. However, it is acceptable to use different device systems, procedures, or methods as long as the same result is obtained. To describe it briefly as an example, electromagnetic waves are irradiated onto a laminated sheet having a metal reflector made of aluminum or the like on the back surface using the coaxial waveguide method or the free space method, and the intensity of the electromagnetic waves reflected back from the laminated sheet is measured and calculated. The frequency is swept to measure the reflection attenuation at each frequency, and in the frequency-reflection attenuation curve plotted with the reflection attenuation on the vertical axis and frequency on the horizontal axis, multiple peaks may be obtained, but the attenuation of the reflection attenuation peak with the largest peak intensity (attenuation) among them is focused on. The peak top referred to here is the point where the sign (slope) of the tangent line of the reflection attenuation spectrum reverses from positive to negative or from negative to positive—that is, the point where a line parallel to the X-axis is tangent.The amount of reflection attenuation at the reflection attenuation peak is expressed as the difference between the amount of reflection attenuation at the peak top and the amount of reflection attenuation at the base line at the frequency indicating the peak top, when there is only one peak top as shown in FIGS. 1 and 2, and subsequently, the amount of reflection attenuation at the peak top of the reflection attenuation peak is expressed as the amount of reflection attenuation RL [dB]. In addition, even if a peak has a high amount of attenuation at the base line as shown in FIG. 3, if it has a specific peak top, the difference between the base line of the peak top and the amount of attenuation at the peak top is read. On the other hand, when a spectrum such as FIG. 4 is obtained having multiple peak tops including a shoulder peak, it is expressed as the difference between the amount of attenuation corresponding to the peak top and the amount of attenuation at the base line of the entire peak including the multiple peak tops, with respect to the frequency of the peak top with the highest peak among the multiple peak tops.
[0032]
[0033] The reflection attenuation amount RL of the reflection attenuation peak expressed in this manner must have a value of 5.0 dB or higher. A reflection attenuation amount RL of less than 5.0 dB means that the electromagnetic wave transmittance is higher than 30%, because it is equivalent to the reflection attenuation amount Γ when following Equation (1) and when the reflection attenuation amount of the baseline is 0 dB. Therefore, a laminated sheet with a reflection attenuation amount RL of the reflection attenuation peak of less than 5.0 dB cannot be said to have sufficient electromagnetic shielding properties. In the laminated sheet of the present invention, the reflection attenuation amount RL at the reflection attenuation peak with the largest reflection attenuation amount is preferably 15.0 dB or higher, more preferably 20.0 dB or higher, and even more preferably 30.0 dB or higher. When the reflection attenuation RL at the peak top, where the reflection attenuation is maximum, is approximately 30.0 dB, it indicates that the incident electromagnetic waves are 99.9% shielded compared to the electromagnetic shielding performance of the frequency band before and after the peak, and it can be said that it possesses very high electromagnetic shielding performance. Although there is no specific upper limit, it is desirable that it be 100 dB or less. Furthermore, the width of the frequency band where the reflection attenuation RL at the peak top, where the reflection attenuation is greatest, exceeds 5.0 dB is desirable because it spans as wide a frequency band as possible while exhibiting steep yet high electromagnetic shielding performance, thereby reducing fluctuations in the frequency band caused by thickness non-uniformity of the laminated sheet. Specifically, the width of the frequency band where the reflection attenuation amount RL of the reflection attenuation peak with the largest reflection attenuation amount at the peak top exceeds 5.0 dB is preferably at least 1.0 GHz, more preferably at least 3.0 GHz, and even more preferably at least 5.0 GHz. As an upper limit, it is preferably at least 20.0 GHz. The reflection attenuation amount RL of the reflection attenuation peak with the largest reflection attenuation amount at the peak top is 5.In order to achieve a high value of 0dB or higher, from the perspective of the composition of the laminated sheet, it can be achieved by having a large number of layers, having small non-uniformity of the layer thickness, and increasing the overall thickness of the sheet, and from the perspective of the additive, by using conductive materials and / or materials that exhibit high conductivity / magnetism, and increasing the concentration of these.
[0034] In the laminated sheet of the present invention, when the reflection attenuation amount RL of the reflection attenuation peak with the largest reflection attenuation amount at the top of the reflection attenuation peak is denoted as RL [dB], the frequency representing said reflection attenuation amount is denoted as f [GHz], and the total thickness of the laminated sheet is denoted as t [mm], it is preferable that RL / (t×f) is 0.2 or more and 15 or less. Compared to the prior art, the laminated sheet of the present invention has one feature in that, by alternately laminating a layer with a low dielectric constant and a layer with a high dielectric constant, the sheet thickness can be reduced and formability can be imparted compared to conventional single-layer or low-layer sheets. This feature applies to sheets targeting any frequency band. However, since there is a trade-off relationship between thickness and frequency, in the configuration of laminated sheets exhibiting the same dielectric constant, the theoretical thickness tends to decrease when the frequency band is shifted toward the high frequency side. In this regard, the effect of the thin film exceeding the volume law of the laminated sheet of the present invention cannot be explained solely by the relationship between the reflection attenuation amount RL and the thickness t (e.g., RL / t, etc.), and it is important that the aforementioned relationship of the three elements—frequency f, laminated sheet thickness t, and reflection attenuation amount RL of the reflection attenuation peak—is superior to that of the prior art. RL / (t×f) is more preferably 0.45 or higher and 12 or lower, and most preferably 0.75 or higher and 10 or lower. If RL / (t×f) is lower than 0.2, the reflection attenuation amount RL is low, so sufficient electromagnetic shielding performance to be used for electromagnetic shielding purposes is not obtained, or there is electromagnetic shielding performance, but the thickness is too high, so it does not exhibit sufficient performance exceeding the volume law. When RL / (t×f) is higher than 15, even though the reflection attenuation amount is high, the thickness is excessively thin, so the lamination precision and film-forming ability of the laminated sheet may deteriorate due to the high concentration addition of conductive material and / or magnetic material.In order for RL / (t×f) to satisfy a desirable range, the effect is enhanced by combining the following elements: a state in which dielectric polarization occurs due to a high number of laminated sheets; a state in which non-uniformity of layer thickness is low; a configuration in which the dielectric constant can be freely designed using multiple types of conductive materials; and a configuration in which the real and imaginary parts of the dielectric constant of the layer exhibiting high dielectric constant satisfy the dielectric constant relationship described below. The desirable conditions for each element are as described in this specification.
[0035] It is preferable that the reflection attenuation peak with the largest amount of reflection attenuation among the reflection attenuation peaks of the laminated sheet of the present invention exists in the frequency band of 1 to 100 GHz. When the laminated sheet of the present invention is used for electromagnetic shielding applications at high frequencies that are difficult to target with conventional conductive reflection technology or magnetic absorption technology, it is preferable to have a maximum attenuation peak in the GHz frequency band. To this end, it is most preferable to form a dielectric absorption type laminated sheet by using the conductive material or dielectric material described below as the material contained in the laminated sheet. Generally, to shield the near-field corresponding to a frequency band of less than several GHz, a sheet containing a magnetic material such as a metal represented by silver or copper, or a metal oxide including ferrite, is used in a dielectric substrate. However, when targeting the high frequency band of the GHz band, it is usually necessary to cover by containing a high concentration of magnetic material due to the characteristic known as the Snoek limit, which is unique to magnetic materials, where magnetic loss in a frequency band higher than a specific frequency is not obtained. Although there are conventional technologies that use special materials such as ε iron oxide, the materials are expensive and require high concentrations of addition, so they may be inferior in terms of cost and film-forming properties compared to cases where conductive materials are used. When producing laminated sheets by melt extrusion, thixotropic properties resulting from the high concentration of filler are unavoidable, and defects in the metal parts of the extruder may occur due to the added magnetic material. Therefore, when producing laminated sheets in a melt extrusion process with a low concentration of filler, in order to obtain electromagnetic shielding properties in the GHz frequency band, it is desirable to obtain electromagnetic shielding properties in the high-frequency band by absorbing electromagnetic waves through the inclusion of a conductive material or a conductive / magnetic composite material.When targeting a frequency band of several GHz by using magnetic materials in combination, it is desirable to use a metal material with a high aspect ratio, which enables energy loss of electromagnetic waves due to high permeability. By adding a material with a high aspect ratio to a laminated sheet, it is possible to achieve alignment of the material in the plane direction, which is difficult with conventional single-layer films, and the material can be made to exhibit shielding properties even in the GHz frequency band. The aspect ratio can be expressed as the ratio of the length in the thickness direction of the material to the length of the major axis in the plane direction. If the former is denoted as t1 and the latter as t2, it is desirable to set t1 / t2 to be 0.001 or greater and 0.95 or less, and more desirable to set it to be 0.01 or greater and 0.1 or less. If the aspect ratio is less than 0.001, the magnetic material becomes excessively thin, so the material may deform or break during the compounding or film-making process, and the effect of the magnetic material may not be obtained.
[0036] The laminated sheet of the present invention has a surface resistance value [Ω / □] of at least one outermost surface of 1.0×10 5It is desirable to have the above. When using a laminated sheet as an electromagnetic wave absorbing sheet, it is desirable to suppress the reflection of electromagnetic waves at the interface between the air layer and the outermost layer of the laminated sheet in order to efficiently propagate electromagnetic waves within the laminated sheet and to lose the energy of the electromagnetic waves within the laminated sheet. When electromagnetic waves are incident perpendicularly, the reflectance R of the electromagnetic waves at the interface of two regions X and Y having different permittivity (ε) and permeability (μ) is expressed as Equation (2). When focusing on the interface reflection between the air layer and the outermost layer of the laminated sheet, it is particularly affected by the difference in the ratio of the permittivity (ε) and permeability (μ) of the air layer and the outermost layer of the laminated sheet. Since the permittivity (ε) and permeability (μ) of the air layer are 1, it is effective to make the ratio of the permittivity ε and permeability μ of the outermost layer of the laminated sheet close to 1 in order to suppress electromagnetic wave reflection. Specifically, it is desirable to use a resin with low dielectric constant and low permeability so that conductivity and permeability are close to values of the air layer, and to form a structure that does not contain either conductive or magnetic materials. Regarding the use of dielectric constant and permeability as indicators of insulation and conductivity, since it is difficult to measure each layer individually in the case of the laminated sheet of the present invention, it is preferable to use surface resistance values that show an approximate correlation to express the insulation and conductivity of individual layers. In the present invention, these values are expressed in accordance with JIS standards using high-resistivity meters and low-resistivity meters manufactured by Mitsubishi Chemical Corporation. As for the surface resistance value [Ω / □], which is an indicator of conductivity that is unlikely to cause surface reflection of electromagnetic waves, 1.0 × 10⁻⁶ 5 It is desirable to show [Ω / □] or higher, and more preferably 1.0×10⁻⁶ 9 [Ω / □] or higher, more preferably 1.0×10 13[Ω / □] or greater. The method of keeping the surface resistance value of the outermost surface within the above range is not particularly limited, but methods such as reducing or not including the conductive / magnetic material or conductive polymer component contained in the layer having the outermost surface may be cited. The surface resistance value is 1.0×10 5 A layer exhibiting [Ω / □] or higher may be located on the layer on the side where electromagnetic waves are incident during mounting, and while it may be placed on at least one side, it is more preferable to be located on the outermost surfaces of both sides. A surface resistance value of 1.0 × 10⁻⁶ 5 [Ω / □] or higher can be achieved by designing the layer located on the surface to have a low concentration of conductive material and / or magnetic material, or not to include a polymer or additive that exhibits conductivity as a resin.
[0037]
[0038] Also, μ X and ε X and represent the permittivity and permeability of region X, respectively, and μ Y and ε Y represents the permittivity and permeability of region Y, respectively.
[0039] The laminated sheet of the present invention is preferably formed by including a conductive material in layer A or layer B. The conductive material may contain only one type, or multiple types of conductive materials may be used in combination.
[0040] The conductive material can be appropriately selected from organic carbon-based materials suitable for melt extrusion due to the small size of the primary particles. Of course, the conductive material does not need to be limited to organic carbon-based materials, and it may also be used in combination with electromagnetic shielding materials or dielectric materials mainly composed of inorganic components other than organic carbon-based materials, as described later. If a laminated sheet is formed using an extruder using only electromagnetic shielding materials or dielectric materials mainly composed of inorganic components, it is necessary to add the electromagnetic shielding material in a high concentration to obtain electromagnetic shielding performance due to conductivity / magnetism, and problems such as material crushing or equipment failure may occur due to friction between the metal of the equipment and the conductive material. Therefore, it is desirable that at least one of the conductive materials includes an organic carbon-based material with carbon as the main component. Having carbon as the main component means that the molar ratio of carbon in the total elements constituting the conductive material is 50 mol% or more, preferably 80 mol% or more, more preferably 90 mol% or more, and particularly preferably 95 mol% or more.
[0041] As organic carbon-based conductive materials, examples include carbon black (spherical carbon) such as acetylene black, channel black, lamp black, thermal black, Ketjen black, furnace black, etc.; carbon nanotubes, which are cylindrical carbon such as single-layer nanotubes, multilayer nanotubes, and cup-stacking nanotubes; flat carbon such as graphite, graphite, and graphene; and other materials such as spherical graphite, cylindrical graphite, carbon microcoils, fullerenes, and carbon fibers (long fibers, short fibers). Among these, in order to improve the conductivity of a layer containing a conductive material by utilizing the effect of particle arrangement in the planar direction due to a stacked structure, it is desirable to use conductive carbon black in which a primary structure (linear structure) develops easily. Furthermore, in order to form a stronger conductive path in the layer direction without disrupting the stacking configuration, it is desirable to use carbon nanotubes or flat carbon, which have a uniform structure and a high aspect ratio, in addition to carbon black in which a structure develops in any direction. In particular, materials with size and thickness controlled at the nano level are preferred, and it is more preferable to use carbon black, carbon nanotubes, graphene, graphite, etc.
[0042] This is intended to obtain the effect of enhancing electromagnetic shielding by forming a large amount of micro-dielectric polarization at the interface between the layer of conductive material and the layer of resin substrate, by arranging a conductive material with a high aspect ratio (including a higher-order structure formed) known as the Maxwell-Wagner effect in a direction in which the long axis direction of the material is approximately parallel to the surface of the laminated sheet, and including it in a resin substrate (in particular, a thermoplastic resin substrate such as a polyolefin resin, polyester resin, acrylic resin, or vinyl monomer copolymer resin, which is an example of a resin with low dielectric constant mentioned above), and by making the resin substrate interlocked between the conductive materials within the layer of the resin substrate containing the conductive material. Specifically, the conductive material included in the dielectric resin substrate is aligned approximately parallel to the sheet plane direction through laminar flow or stretching processes by a lamination process, and the polarizations are made to face each other in parallel, like a parallel plate capacitor. Accordingly, when an electric field is applied by irradiating with electromagnetic waves, a large amount of charge tends to accumulate at the interface between the dielectric substrate and the conductive material, thereby increasing the conductivity within the laminated sheet. As a result, when electromagnetic waves are incident, resistance is received by the conductive material, making it easier for electromagnetic energy to be converted into thermal energy, which consequently enhances shielding performance through electromagnetic wave absorption. To achieve this embodiment through lamination or stretching processes, it is preferable to use cylindrical or flat materials with high aspect ratios among the materials described above, carbon nanotubes, or carbon black with high DBP oil absorption as the conductive material.
[0043] Examples of carbon black suitable for use in the present invention include carbon black having a dibutyl phthalate (DBP) oil absorption amount [mL / 100g] of 150 or more. The DBP oil absorption amount [mL / 100g] is an indicator representing the degree of development of the carbon black structure. A material with a high value is desirable because it implies that carbon black particles are easily connected in a straight chain, and thus many voids exist between the structures, allowing conductive paths to be formed and conductivity to be imparted even with a smaller content. The DBP oil absorption amount [mL / 100g] of the carbon black is more preferably 250 or more, and even more preferably 350 or more. When the structure of the carbon black develops and conductive paths are formed, when an electric field is generated by irradiation with electromagnetic waves, charges accumulate at the interface between the dielectric substrate and the conductive material. As a result, the electromagnetic energy is converted into thermal energy by the conductive material acting as an electromagnetic resistor, thereby exhibiting high shielding performance through electromagnetic wave absorption. Although there is no specific upper limit for the DBP oil absorption amount, considering that the structure may be destroyed when dispersed in the polymer material constituting the conductive material, it is preferable that it be 800 [mL / 100g] or less. In addition, the DBP oil absorption amount can be measured in accordance with ASTM D 2414-79. As such conductive spherical carbon, commercially available materials such as acetylene black, furnace black, and Ketjen black can be used.
[0044] As an electromagnetic shielding material consisting mainly of inorganic components other than the conductive material that can be used in the laminated sheet of the present invention, metal elements such as silver, copper, iron, nickel, chromium, aluminum, zinc, and tin, and their metal oxides, metal nitrides, metal carbides, metal borides, metal oxynitrides, metal hydroxides, metal oxyborides, metal carbonyls, and organometallic complexes may be used. In particular, as preferred components, indium tin oxide (ITO), indium zinc oxide (IZO), and stainless steel materials, which are known as transparent conductive metal oxides, or carbonyl iron, hexacyanoferrous iron, amino iron, etc., may be used as organometallic complexes. It is preferable to use these inorganic metal-based magnetic materials as well as expanded flat materials, similar to the carbon material, in order to further enhance the electromagnetic shielding properties in the laminated sheet of the present invention.
[0045] In addition, as an additive used in the laminated sheet of the present invention, a dielectric material having excellent charge accumulation ability may be added. The dielectric material is not a material that has the effect of directly losing the energy of electromagnetic waves by imparting resistance to irradiated electromagnetic waves. However, as described below, in order to shield electromagnetic waves of a specific frequency band, the real term ε of the dielectric constant of the layer exhibiting a relatively high dielectric constant of the laminated sheet h ' and imaginary term ε h It is desirable to control ” within a specific range, and in this case, the real term ε of the permittivity h ' and imaginary term ε h Not only conductive materials that tend to fluctuate numerically in accordance with the addition concentration, but also the real term ε of the permittivity hIt is desirable to use a dielectric material that can selectively improve the complex permittivity value, thereby enabling more precise control of the complex permittivity value. Examples of dielectric materials that can be used here include magnesium oxide, titanium oxide, barium titaniumate, strontium titaniumate, calcium titaniumate, lead zirconate titaniumate, titanium oxide, iron oxide (ferrite), bismuth ferrite, etc., which have a perovskite structure or a rutile structure, but titanium oxide, ferrite, barium titaniumate, etc., are preferred because they are general-purpose and exhibit high permittivity.
[0046] The electromagnetic wave suppression material used in the laminated sheet of the present invention preferably uses two or more types of materials among the above-mentioned organic carbon-based conductive material, electromagnetic shielding material mainly composed of inorganic components, and dielectric material. This is because when controlling the dielectric constant of a layer exhibiting a high dielectric constant, as described later, to a desirable range exhibiting a high amount of electromagnetic wave attenuation, changing only the content concentration of a single material results in the relationship between the real and imaginary terms of the dielectric constant exhibiting only linear behavior on the dielectric plane, making it difficult to control it to a specific range. Therefore, by using materials that exhibit a different linear relationship between the real and imaginary terms of the dielectric constant in combination, it becomes possible to control the real and imaginary terms of the dielectric constant two-dimensionally on the dielectric plane, thereby making it easier to design a laminated sheet with a higher amount of attenuation. At this time, different materials may be used among the conductive materials, or an electromagnetic shielding material mainly composed of inorganic components or a dielectric material may be used in combination in addition to the conductive material. In particular, iron oxide, barium titanium oxide, titanium oxide, and iron carbonyl, which have high complex permittivity, can increase the real part of the complex permittivity without increasing the imaginary part, and can more drastically adjust the permittivity by using them in combination with carbon materials, so they can be preferably used as a second material.
[0047] From the perspective of achieving compatibility between electromagnetic shielding performance and the strength of the laminated sheet itself, it is preferable that the content of these electromagnetic shielding materials be 1 weight% or more and less than 15 weight% when the total components constituting the laminated sheet are set to 100 mass%. Generally, when high conductivity is obtained, it is necessary to increase the content of the conductive material; however, if the content of the conductive material is high, while high conductivity is obtained, film formation and processability are significantly impaired, and the sheet itself may become brittle. Conversely, if the content of the conductive material is excessively low, the effect of electromagnetic shielding may not be sufficiently obtained; therefore, it is preferable that the content of the conductive material be 1 weight% or more and less than 15 weight%. More preferably, it is 1.5 weight% or more and less than 10 weight%, and even more preferably, 2 weight% or more and less than 5 weight%. In addition, when the laminated sheet includes multiple types of electromagnetic suppression materials, the content of the electromagnetic suppression materials is calculated by summing all the electromagnetic suppression materials.
[0048] As described above, the conductive material contained in the laminated sheet of the present invention may be contained in only one of the A layer or the B layer, or in both the A layer and the B layer. However, if both the A layer and the B layer contain the conductive material to form a layer with high conductivity, the effect of dielectric polarization at the interface of each layer of the laminated sheet is not sufficiently obtained, and the laminated sheet as a whole exhibits an effect similar to that of a single-layer electromagnetic shielding material, and thus, there are cases where the electromagnetic shielding properties for only the desired frequency are not obtained. Furthermore, since the conductivity and dielectric constant of the layer located on the surface increase, surface reflection of electromagnetic waves occurs, and compared to a laminated sheet in which the conductive material is contained at the same concentration as the entire laminated sheet and a larger amount of conductive material is contained in the B layer, the effect of electromagnetic wave absorption by the conductive material may be reduced. Therefore, when the laminated sheet is made having a repeating unit of A(BA)n, it is preferable that the amount of conductive material contained in the A layer corresponding to the surface layer is less than the amount of conductive material contained in the B layer not corresponding to the surface layer. More specifically, it is preferable that the total content of conductive materials contained in layer A is 1 weight% or less relative to the total weight of the laminated sheet, and the total content of conductive materials contained in layer B is 1 weight% or more relative to the total weight of the laminated sheet. Even more preferably, the difference in the content of conductive materials between layer A and layer B is large, and in particular, layer A does not contain conductive materials, and layer B contains conductive materials only.
[0049] In addition to the conductive material / magnetic material / dielectric material, the laminated sheet of the present invention may contain, as necessary, a dispersant, a surface modifier, a lubricant, a crosslinking agent, a vulcanization accelerator, an antioxidant, a crystallization nucleating agent, a flame retardant, a light absorber (ultraviolet absorber, pigment, heat absorber, etc.), a flow modifier (plasticizer, thickener), an anti-blocking agent, etc., to the extent that the original properties of the laminated sheet are not impaired. Furthermore, as long as the original properties of the laminated sheet are not impaired, these components may be contained in any of the A layer, the B layer, or layers other than the A layer and the B layer.
[0050] It is preferable that the laminated sheet of the present invention has the A layer on at least one surface layer. By providing the A layer, which has low conductivity, on the surface layer, the reflection effect caused by the B layer, which has a high dielectric constant, is suppressed, and electromagnetic waves irradiated onto the laminated sheet can be efficiently transmitted into the laminated sheet, thereby fully enabling the laminated sheet to exhibit its effect as an electromagnetic wave absorbing sheet. Whether the A layer is placed on only one side of the surface layer or on both sides can be appropriately selected considering the practicality when using the laminated sheet as an electromagnetic wave absorbing material.
[0051] The electromagnetic shielding properties and frequency band of the laminated sheet of the present invention are impedance Z represented by equations (3) and (4). in , and the reflection attenuation amount Γ calculated thereby can be obtained. In addition, as can be seen from the equation, Z in And Γ depends on the permittivity, permeability, and thickness of the entire sheet. Therefore, in order to achieve high electromagnetic shielding performance in a thin film, it is necessary for the product of the real part of the permittivity ε' and the real part of the permeability μ' to have a high value. In addition, in Equations (3) and (4), Z0 represents the characteristic impedance of the atmosphere, d represents the thickness of the laminated sheet, λ represents the wavelength, μ represents the permeability of the entire laminated sheet, and ε represents the permittivity of the entire laminated sheet, respectively, and the value of Z0 is 377Ω.
[0052]
[0053]
[0054] The permittivity and permeability of the entire laminated sheet influence the design of the permittivity of alternating A and B layers because they cause dielectric polarization. Specifically, when the difference in permittivity between A and B layers is sufficiently large, the real part ε of the permittivity of the layer exhibiting a relatively high permittivity... h ' and imaginary part ε h Controlling “ is very effective for adjusting electromagnetic shielding performance. The region exhibiting high electromagnetic shielding performance for a specific frequency band at a specific sheet thickness can be calculated based on Equations (3) and (4). In addition, for the laminated sheet to exhibit high electromagnetic shielding performance, the real part ε of the permittivity of the layer with the relatively higher permittivity among layer A and layer B h ' and imaginary part ε h It is desirable to satisfy the relationship of equation (A) or equation (B).
[0055] (A) ε h "≥1, also 0.17ε h +2.3≤ε h "≤0.27ε h +3.3
[0056] (B) 5≥ε h ≥1, also 0.02ε h +1≤ε h "≤0.07ε h +1.9
[0057] The real part ε of the permittivity of the layer with relatively high permittivity h ' and imaginary part ε h By controlling " to this range, it becomes possible to achieve high electromagnetic shielding performance at a specific frequency, even when the sheet thickness is thin.
[0058] The real part ε' of the permittivity of the laminated sheet of the present invention, the imaginary part ε" described below, and the real part μ' of the permeability can be measured by the method described in the section "Permittivity Measurement" of the Examples. In addition, the real part and imaginary part (ε of the permittivity of each layer h ', ε h "") can be measured by the method described in "Calculation of Permittivity of Each Layer" of the above method and examples. Briefly explained, it is obtained by using a jig of a waveguide or lens antenna to match the frequency to be measured, and calculating the reflection and transmission characteristics of electromagnetic waves when electromagnetic waves emitted from an electromagnetic wave generating device are incident on a sample installed inside the waveguide or between the lens antennas, in accordance with the known S-parameter method. Furthermore, the measuring device or calculation software is not particularly limited as long as it is capable of measurement or calculation; for example, the device described in the examples or the calculation software attached to these devices may be used. In this case, the real term ε' and the imaginary term ε" of the permittivity can be obtained by reading the values automatically calculated by the calculation software.
[0059] The real part ε of the permittivity of the layer with relatively high permittivity h ' and imaginary part ε h A method for controlling "..." to satisfy the relationship of Equation (A) or Equation (B) above may include, for example, using carbon black as a conductive material in which the DBP oil absorption amount is within the range described below, using barium titanate, ferrite oxide, or titanium oxide as a dielectric material, using iron carbonyl as a magnetic material, or improving the dielectric constant by using a conductive material such as graphite or graphene with a high aspect ratio. In particular, to satisfy Equation (A), the real part ε of the dielectric constant h ' and imaginary part ε h Since it is required to increase all of ”, it is desirable to use carbon black, and in order to satisfy equation (B), the imaginary part ε of the permittivity hSince a low aspect ratio is required, this can be achieved by using at least one type of dielectric material such as barium titaniumate, ferrite, or titanium oxide, and a conductive material with a high aspect ratio such as graphite or graphene, either alone or in combination. Additionally, this can be achieved by using the stretching method described later to reduce the thickness of each layer, or by increasing the number of layers of a multilayer laminated sheet by interposing a feed block having a slit, thereby dispersing and orienting the conductive material and / or magnetic material in the plane direction of the sheet.
[0060] The laminated sheet of the present invention preferably has a half-width of the reflection attenuation peak with the largest reflection attenuation amount at the peak top, fΔ [GHz], and a ratio of RL / fΔ to the reflection attenuation amount at the peak top with the largest reflection attenuation amount at the peak top, RL [dB], which is 5.0 or higher. RL / fΔ is an indicator representing the steepness of the reflection attenuation peak, and by setting RL / fΔ to this range, the material can be made to shield only the desired electromagnetic region when mounted on electronic devices or communication devices. RL / fΔ can be increased by reducing the non-uniformity of the layer thickness of layer A and / or layer B, or by increasing the dielectric constant difference between the high-conductivity layer and the low-conductivity layer through the combination of resins, the use of a conductive material with high DBP oil absorption or a high aspect ratio, or an increase in the number of layers, and the ratio RL / fΔ is more preferably 10.0 or higher, and even more preferably 20.0 or higher. If the RL / fΔ at the peak of maximum reflection attenuation is lower than 5, it implies a material that shields electromagnetic waves over a wide frequency band, similar to conventional products. However, if one wishes to attenuate only electromagnetic waves of a specific frequency, it may result in shielding of electromagnetic waves in undesirable frequency bands. Although there is no specific upper limit for the RL / fΔ at the peak of maximum reflection attenuation, if the steepness is very high, the peak top position may shift sensitively due to slight changes in laminated sheet thickness or the concentration of conductive material, potentially failing to achieve the desired electromagnetic shielding performance. Therefore, it is desirable for the RL / fΔ at the peak of maximum reflection attenuation to be less than 200. The half-width depends on the frequency of the reflection attenuation peak, where the amount of reflection attenuation at the peak top is the greatest, but the smaller one is preferred as a laminated sheet of the present invention capable of cutting only a specific frequency, and specifically, the half-width fΔ[GHz] is preferably 10.0 or less, more preferably 5.0 or less, and even more preferably 2.0 or less.
[0061] In addition, in the laminated sheet of the present invention, the frequency of the peak of the reflection attenuation peak, which has the largest reflection attenuation amount at the peak top, is determined by the dielectric constant / permeability of the conductive layer, so it can be controlled not only by the type and content of the conductive material but also by the thickness of alternating A and B layers with different conductivity. Since electronic devices, communication devices, and transportation vehicles have different frequencies to be attenuated and frequencies not to be attenuated depending on their application, the laminated sheet of the present invention can easily control the frequency for which electromagnetic shielding is required, so it can be suitably used in electronic devices, communication devices, and transportation vehicles.
[0062] In the laminated sheet of the present invention, it is preferable that the coefficient of variation tBσ / tB is 0.3 or less, where the average value of the layer thickness of layer B is tB [mm] and the standard deviation is tBσ [mm]. As described above, in a configuration where layer A is located on the surface layer and is a layer with a surface resistance value higher than that of layer B, layer B, which exhibits conductivity, becomes the main layer responsible for electromagnetic shielding by absorbing electromagnetic waves; however, if the thickness of these layers varies between layers, the dielectric constant differs for each layer, causing variations in the frequency of electromagnetic waves for which shielding is obtained. It is desirable to align the thickness of layer B, which exhibits conductivity, so that the coefficient of variation tBσ / tB falls within the range described above, because layers exhibiting a constant dielectric constant overlap, thereby enabling steepness in electromagnetic shielding and obtaining frequency selectivity with a high amount of electromagnetic attenuation. It is preferable that the coefficient of variation tBσ / tB, which indicates variation in layer thickness, is 0.2 or less, and more preferably 0.1 or less. In the case of laminated sheets composed of thermoplastic resin, the coefficient of variation can be lowered by using a slit-type feed block rather than increasing the number of layers using a mixer. Although there is no specific limit on the lower limit of the coefficient of variation tBσ / tB, it is practical to make it 0.01 or higher in light of the productivity of the laminated sheet.
[0063] In addition, although there is no limitation on the thickness of the A layer of the laminated sheet of the present invention, if the A layer is thinner than the distance at which the conductive material included in the B layer exists, the effect of macro-dielectric polarization between the A layer exhibiting dielectric properties and the B layer exhibiting conductivity may not be obtained, and the electromagnetic loss may be reduced. Therefore, when the average thickness of the A layer is denoted as tA [mm], it is preferable to design it such that tA ≥ tB, as this allows for sufficient separation between adjacent B layers.
[0064] As a preferred embodiment of the present invention, an electromagnetic shield having the aforementioned laminated sheet and a reflector can be provided. The reflector is a plate-shaped material having the function of reflecting electromagnetic waves. By combining it with the opposite side of the laminated sheet to the electromagnetic wave incident surface, the electromagnetic waves are reciprocated within the laminated sheet, thereby increasing the electromagnetic wave absorption efficiency. On the other hand, if the reflector is placed on the front surface, it is also possible to reflect a certain amount of electromagnetic waves from the surface of the reflector and rapidly shield a portion of the transmitted electromagnetic waves within the laminated sheet. To fully utilize the electromagnetic wave absorption characteristics of the laminated sheet of the present invention, the former configuration is more preferable.
[0065] As long as the reflector is capable of reflecting electromagnetic waves, the constituent material is not particularly limited. Examples of constituent materials include metals such as aluminum, copper, iron, and gold, alloys such as stainless steel, and carbon films. As long as the reflector is made containing metal or alloy, or contains carbon, the shape and thickness are not limited. The shape must be adapted to the material to which it is applied, but it may be flat, curved, hemispherical, or plate-like.
[0066] Examples of reflectors include plate reflectors comprising metal, alloy, and carbon; laminated type reflectors in which a film made of metal, alloy, and carbon is formed on the surface of a polymer film, sheet, or plate; composite type reflectors in which metal, alloy, and carbon are dispersed within a polymer film, sheet, or plate; and composite type reflectors comprising a mesh made of metal or alloy within a polymer film, sheet, or plate. Furthermore, in the present invention, if a support or housing for each application comprises metal, alloy, carbon, etc., it may be used as a reflector as is.
[0067] As a preferred embodiment of the present invention, electronic devices or communication devices having the aforementioned laminated sheet or the aforementioned electromagnetic shielding body may be used for purposes such as preventing false images caused by electromagnetic waves used in 4G / 5G communication, wireless LAN, and intelligent collision avoidance (ITS) radar, reducing unnecessary radiation of electromagnetic waves from electronic devices provided inside housings such as computers, mobile phones, wireless devices, medical devices, and vehicle bumpers, and preventing device malfunction caused by radiation from adjacent devices. Furthermore, any electronic device or communication device using a frequency in the GHz band may be equipped with the laminated sheet of the present invention and used, not limited to the above.
[0068] In addition, as a preferred embodiment of the present invention, means of transportation such as vehicles, aircraft, or ships having the aforementioned laminated sheet or the aforementioned electromagnetic shield body, walls of structures such as buildings, tunnels or guardrails, highways, bridges, or steel towers, and communication facilities such as telegraphs or telephones may be cited. As a method of applying the laminated sheet of the present invention, methods such as attaching it directly with an adhesive or the like, or attaching it to structures such as floors, ceilings, walls, or columns with other sheets, shield plates, or panels interposed, may be used. Furthermore, it may also be used as a wall material or window material for a shield room to prevent the effects of electromagnetic jamming or noise from the outside.
[0069] Next, a preferred method for manufacturing an alternating lamination unit of the laminated sheet of the present invention is described below. Of course, the present invention is not to be interpreted as being limited to the examples described below.
[0070] An example of a method for manufacturing an alternating laminated unit when using rubber or thermoplastic elastomer, etc., as the base polymer is provided. A predetermined amount of a conductive material is mixed into the base polymer, and a conductive material-containing polymer is produced by mixing and incorporating it using a known apparatus such as a kneader, Banbury mixer, mill mixer, roll mill, jet mill, or ball mill. The base polymer alone or the produced conductive material-containing polymer is formed into a sheet of a desired thickness by rolling with a batch press or melt extrusion, respectively. Subsequently, the sheet corresponding to layer A and the sheet corresponding to layer B produced are overlapped, pressed, or laminated to obtain a desired laminated alternating laminated unit. The fusion temperature depends on the resin used, but a temperature range of 150°C to 400°C is preferred, and 250°C to 380°C is more preferred.
[0071] An example of a method for manufacturing an alternating laminated unit using a flexible thermoplastic resin, which is preferably used in the present invention, is described below. A thermoplastic resin prepared in the form of pellets and a predetermined amount of conductive material are kneaded using a twin-screw extruder, extruded into a gut, cooled in a water bath, and then cut with a chip cutter to form a master pellet containing the conductive material. At this time, the conductive material may be dry-blended with the resin and then metered and fed from a hopper, or side-fed into the molten resin using a side feeder from any position of the extruder. It can be appropriately selected according to the specific gravity or shape of the conductive material used.
[0072] Each thermoplastic resin constituting layers A and B is dried in hot air or under vacuum and then supplied to a separate extruder. Each resin, heated and melted above its melting point in the extruder, is discharged in a uniform extrusion volume using a gear pump or the like, and foreign matter or modified resin is removed through a filter or the like. These resins are formed into a desired shape in a die through a multilayer stacking device capable of stacking a desired number of layers, and then discharged as a sheet. The sheet discharged from the die is extruded onto a cooling body, such as a casting drum, and cooled and solidified to obtain a cast sheet. At this time, since the cast sheet itself exhibits conductivity, a method of rapidly cooling and solidifying by blowing air from a slit-shaped, spot-shaped, or planar device to make it adhere to a cooling body, such as a casting drum, or a method of rapidly cooling and solidifying by making it adhere to a cooling body using a nip roll is preferred.
[0073] As described above, a multi-manifold die, feed block, or static mixer can be used as a multi-layer stacking device; however, to efficiently obtain the multi-layer stacking structure of the present invention, it is particularly desirable to use a feed block having a fine slit. By using such a feed block, the device does not become excessively large, so the amount of foreign matter generated due to thermal degradation is low, and high-precision stacking becomes possible even when the number of layers is extremely large. Furthermore, the stacking precision in the width direction is significantly improved compared to conventional technology. In addition, since the thickness of each layer can be adjusted by the shape (length, width) of the slit in this device, it becomes possible to achieve any desired layer thickness. Furthermore, a method of increasing the number of layers by overlapping them through a static mixer after forming a stack with a feed block to double the number of layers can also be suitably utilized. In this case, since the layer thickness of each overlapping stack becomes completely identical, it is suitable for the concept of the present invention, which is desirable to align the stacking thicknesses.
[0074] The obtained cast sheet can be continuously biaxially stretched in the long side direction and the width direction as needed. The stretching may be performed sequentially or simultaneously. Additionally, further stretching may be performed in the long side direction and / or the width direction.
[0075] First, the case of sequential biaxial stretching will be explained. Here, stretching in the long side direction refers to stretching to impart molecular orientation in the long side direction to the sheet. It is typically performed by the difference in peripheral speed of the rolls, and may be carried out in a single stage or in multiple stages using multiple pairs of rolls. The stretching ratio varies depending on the type of resin, but is typically 1.1 to 15 times, and 1.5 to 4 times is particularly preferred. In addition, the stretching temperature is preferably set within the range of the glass transition temperature of the resin constituting the alternating laminated unit to the glass transition temperature + 100°C.
[0076] For the alternating stacked unit stretched in the long side direction obtained in this way, surface treatments such as corona treatment, flame treatment, or plasma treatment may be performed as needed, and then a primer layer may be formed to improve adhesion with the film stacked on top. In an inline coating process, the primer layer may be applied to one side, or to both sides simultaneously or sequentially on one side.
[0077] Stretching in the width direction refers to stretching to impart a width-direction orientation to the sheet. Typically, a tenter is used to convey the sheet while gripping both ends with clips, thereby stretching it in the width direction. The stretching ratio varies depending on the type of resin, but typically 1.1 to 15 times is preferred, and 1.5 to 6 times is particularly preferred. Additionally, the stretching temperature is preferably the glass transition temperature of the resin constituting the alternating laminated unit to the glass transition temperature + 120°C. The alternating laminated unit biaxially stretched in this manner is subjected to heat treatment above the stretching temperature and below the melting point within the tenter, uniformly slow-cooled, and then cooled to room temperature before being wound up. Furthermore, if necessary, to impart a low orientation angle and thermal dimensional stability to the sheet, relaxation treatment in the long side direction and / or the width direction may be combined with slow cooling from the heat treatment.
[0078] Next, the case of simultaneous biaxial stretching will be explained. In the case of simultaneous biaxial stretching, the resulting cast sheet may be subjected to surface treatments such as corona treatment, flame treatment, or plasma treatment as needed, and then functions such as deactivation, adhesion, and antistatic properties may be imparted by inline coating. In the inline coating process, the adhesion layer may be applied to one side of the alternating stacking unit, or applied to both sides of the alternating stacking unit simultaneously or sequentially on one side.
[0079] Next, the cast sheet is guided to a simultaneous two-axis tenter, and the sheet is conveyed while gripping both ends with clips to stretch it simultaneously in the long side direction and the width direction. As for the simultaneous two-axis stretching machine, there are pantograph, screw, drive motor, and linear motor types; however, a drive motor or linear motor type is preferred because the stretching ratio can be arbitrarily changed and relaxation treatment can be performed at any location. The stretching ratio varies depending on the type of resin, but typically, an area ratio of 2 to 50 times is preferred, and an area ratio of 4 to 20 times is particularly preferred. The stretching speed may be the same, or stretching may be performed in the long side direction and the width direction at different speeds. In addition, the stretching temperature is preferably the glass transition temperature of the resin constituting the alternating stacking unit to the glass transition temperature + 120°C.
[0080] In order to impart flatness and dimensional stability to the alternating laminated unit simultaneously biaxially stretched in this manner, it is desirable to continuously perform heat treatment in a tenter at a temperature above the stretching temperature and below the melting point. During this heat treatment, in order to suppress the distribution of the main orientation axis in the width direction, it is desirable to perform relaxation treatment in the long side direction instantaneously immediately before and / or immediately after entering the heat treatment zone. After heat treatment in this manner, the unit is uniformly slow-cooled, cooled to room temperature, and wound. Additionally, if necessary, relaxation treatment in the long side direction and / or width direction may be performed during slow cooling from the heat treatment. Relaxation treatment in the long side direction is performed instantaneously immediately before and / or immediately after entering the heat treatment zone.
[0081] To obtain the desired electromagnetic shielding properties, the fabricated alternating stacked units may be bonded together with identical alternating stacked units, or with alternating stacked units having different thicknesses and compositions, by interposing an adhesive sheet, a pressure-sensitive adhesive sheet, double-sided tape, etc.
[0082] In addition, layers with different dielectric constants may be laminated on the outermost surface of the alternating laminated unit for purposes such as increasing electromagnetic wave transmittance or causing electromagnetic wave reflection. At this time, a coating layer containing a material exhibiting suitable conductivity / magnetism may be applied, or other resin layers / mesh layers may be laminated by interposing an adhesive sheet, or resin / metal layers may be laminated using sputtering (planar or rotary magnetron sputtering, etc.), evaporation (electron beam evaporation, etc.), chemical vapor deposition, organometallic chemical vapor deposition, plasma-enhanced / supported / activated chemical vapor deposition, ion sputtering, etc., which are used as film metal coating technologies.
[0083] The present invention will be described below according to examples, but the present invention is not to be interpreted as being limited to these examples. Each characteristic was measured by the following method.
[0084] (Methods for measuring characteristics and evaluating effects)
[0085] The method for measuring characteristics and evaluating effects in the present invention is as follows.
[0086] (1) Layer thickness, number of layers, stacking structure
[0087] The layer composition of the laminated sheet was determined by observing a differential interference microscope or a transmission electron microscope (TEM) on a sample cross-sectioned using a microtome, corresponding to the layer thickness of each layer constituting the laminated sheet. In the former case, more specifically, when the thickness of each layer constituting the laminated sheet was 1 μm or more, a Leica differential interference microscope "DMLBHC" was used to observe the cross-section of the laminated sheet under conditions of 1000x magnification (10x eyepiece, 100x objective lens), and cross-sectional images were taken to measure the layer composition and the thickness of each layer. The measurement distance was determined using the particle size analysis software "Macview" (Mountek), and the layer thickness was measured by determining the vertical distance between layer interfaces where contrast differences could be clearly identified. Data were measured at five random locations, and the average value of the thickness of each layer was used as the actual measurement data. For the particle major axis, the longest distance of the higher-order structure formed by the particle identified in the image was measured at a total of 100 points, and the averaged data was used. For the latter transmission electron microscope (TEM) observation, a transmission electron microscope H-7100FA model (manufactured by Hitachi Seisakusho Corp.) was used to observe the cross-section of the laminated sheet under conditions of an acceleration voltage of 75 kV, and cross-sectional photographs were taken to measure the layer composition and the thickness of each layer. In addition, in some cases, staining techniques using RuO4 or OsO4 were used to obtain high contrast. Furthermore, based on the thickness of the thinnest layer (thin film layer) among all layers introduced in a single image, observations were performed at magnifications of 100,000x when the thin film layer thickness was less than 50 nm, 40,000x when the thin film layer thickness was 50 nm or more and less than 500 nm, and 10,000x when it was 500 nm or more, to determine the layer thickness, number of layers, and stacking structure. In addition, the thickness of each layer of the B layer in a specific cross-section among the obtained images was read, and the average value and standard deviation of the layer thickness were calculated.The average value and standard deviation of the layer thickness of layer B at five other cross-sections were calculated, and the average of the five calculated values was adopted as the average value tB[mm] and standard deviation tBσ[mm].
[0088] (2) Measurement of reflection attenuation
[0089] Measurements were performed by changing the measurement unit as follows, in accordance with the measurement frequency band. In addition, based on the obtained results, a frequency-reflection attenuation curve was obtained, plotted with the reflection attenuation on the vertical axis and frequency on the horizontal axis.
[0090] (2-1) Frequency band of 1 GHz to 40 GHz
[0091] The reflection attenuation of the laminated sheet was measured using a Vector Network Analyzer (E8361A) manufactured by Agilent Technologies, Inc. Measurements were taken using a donut-shaped coaxial waveguide with an outer diameter of φ7 mm and an inner diameter of φ3.04 mm for the frequency band from 0.5 GHz to 18 GHz, a rectangular waveguide with dimensions of 4.32 mm × 10.67 mm for the frequency band from 18 to 26.5 GHz, and a rectangular waveguide with an internal dimension of 3.56 mm × 7.11 mm for the frequency band from 26.5 to 40 GHz. The frequency interval width during measurement was set to allow measurements at 200 frequencies within each frequency band. A 3 mm aluminum metal plate was installed on the back of the laminated sheet sample, ensuring that incident electromagnetic waves undergo total internal reflection when there is no electromagnetic wave absorption by the laminated sheet. S, which represents the ratio of the intensity of the reflected electromagnetic waves to the intensity of the incident electromagnetic waves, 11 The reflection attenuation peak was analyzed using the S parameter value.
[0092] (2-2) Frequency band of 40 to 110 GHz
[0093] A measurement sample was prepared by bonding an aluminum metal plate to the back surface of a square laminated sheet with sides of 150 mm. Using the LAF-26.5B, a lens antenna type oblique incidence type electromagnetic wave absorber (electromagnetic wave absorbing material) and reflection attenuation measuring device manufactured by KICO, electromagnetic waves were irradiated at an oblique incidence of 15° in accordance with JIS R 1679, and the reflection attenuation was measured for each frequency band of 33 to 50 GHz (WR-22), 50 to 75 GHz (WR-15), and 75 to 110 GHz (WR-10). In addition, although values for the frequency band of 33 to 40 GHz can also be obtained using this measurement method, the reflection attenuation in the frequency band of 33 GHz or higher and less than 40 GHz was measured using the measurement data from (2-1).
[0094] (3) Permittivity measurement
[0095] For the laminated sheet, the measurement unit and measurement method were changed for each measurement frequency and analyzed as follows.
[0096] (3-1) 1GHz to 40GHz frequency band
[0097] A vector network analyzer (E8361A) manufactured by Agilent Technologies, Inc. was used. For the frequency band from 0.5 GHz to 18 GHz, a donut-shaped coaxial waveguide with an outer diameter of φ7 mm and an inner diameter of φ3.04 mm was used; for the frequency band from 18 to 26.5 GHz, a rectangular waveguide with dimensions of 4.32 mm × 10.67 mm was used; and for the frequency band from 26.5 to 40 GHz, a rectangular waveguide with an internal shape of 3.56 mm × 7.11 mm was used. A laminated sheet sample was punched and inserted vertically into each waveguide for measurement. The frequency interval width during measurement was set to allow measurement at 200 frequencies in each frequency band. The complex permittivity was analyzed using the analysis software N1500A-001 included with the device.
[0098] (3-2) 40 to 110 GHz frequency band
[0099] A square laminated sheet with sides of 150 mm was used. Using the LAF-26.5A lens antenna type relative permittivity and attenuation measuring device manufactured by K.I.K.M. using the frequency change method, the complex permittivity was measured for each frequency band from 33 to 50 GHz (WR-22), 50 to 75 GHz (WR-15), and 75 to 110 GHz (WR-10). In addition, values for 33 to 40 GHz were also measured in this measurement method, but for the complex permittivity in the frequency band from 33 GHz to less than 40 GHz, the measurement data from (3-1) was used.
[0100] (4) Surface resistance measurement
[0101] (4-1) High Resistance Measurement
[0102] High resistance region (1.0×10 6 Up to 1.0×10 13 [Ω / □]) was measured using a high resistivity meter Hiresta-UP (MCP-HT450) manufactured by Mitsubishi Chemical Corporation. A URS probe (MCP-HTP14) was pressed onto the surface of a laminated sheet cut to a square of 10 cm, and the resistance value was measured in accordance with JIS K 6911 (1995). Measurements were taken at 5 samples while varying the measurement position, and the arithmetic mean of the 5 obtained measurements was used.
[0103] In addition, when measuring the surface resistance value of the inner layer, the surface was polished with a polishing device to the thickness of the outermost layer confirmed by a transmission electron microscope, and then the probe was pressed to take the measurement.
[0104] (4-2) Measurement of low resistance value
[0105] Low resistance region (1.0×10 6 Up to 1.0×10 -1[Ω / □]) was measured using a low resistivity meter Loresta-EP (MCP-T360) manufactured by Mitsubishi Chemical Corporation. An ASP probe (MCP-TP03P) was pressed against the surface of a laminated sheet cut to a square of 10 cm, and the resistance value was measured in accordance with JIS K 7194. Measurements were taken at 5 samples while varying the measurement position, and the arithmetic mean of the 5 obtained measurements was used.
[0106] (5) DBP oil absorption
[0107] The laminated sheet was dissolved in a solvent capable of dissolving the substrate resin, and the extracted and separated carbon-based conductive particles were measured in accordance with ASTM D2414-79 using a Brabender Type C oil-absorbing system. The carbon-based conductive particles fed into the mixer were rotated at a speed of 125 [min -1 While mixing with ], DBP was added dropwise at a dropping rate of 4 [mL / min], and the amount of DBP absorbed was read based on the obtained viscosity curve.
[0108] (6) Calculation of permittivity of each layer
[0109] Macro software was developed and used to calculate the impedance when the configuration of the laminated sheet is substituted into an equivalent electrical circuit, by substituting the values of the permittivity, permeability, and layer thickness of layers A and B. The obtained impedance Z inA macro was created to continuously calculate the reflection attenuation amount Γ over a constant frequency band by substituting it into Equation (4), which is based on the non-reflective condition equation and the reflection attenuation amount. Then, the permittivity and permeability of each layer were set to match the reflection attenuation spectrum measured by the method described in (2), and the permittivity and permeability of each layer were determined by reading the permittivity and permeability at which the reflection attenuation spectrum was most approximate. In addition, when it is difficult to calculate the permittivity, a single-layer sheet was fabricated with the same composition as the layer exhibiting a relatively high permittivity in the example, and the frequency exhibiting the minimum value of the transmission attenuation amount was determined by the frequency change method using the vector network analyzer described above. The permittivity was calculated from the fact that this minimum value is an integer multiple of 1 / 2 of the operating wavelength transmitted through the sheet thickness. The same value can also be verified in the attached software (SFW05) of the KICO frequency change method free-space measurement permittivity measurement system (Model No. DPS10).
[0110] Examples
[0111] (Reference Example 1)
[0112] A square sheet A with a thickness of 0.5 mm and a side length of 200 mm was produced by press molding using 100 parts by weight of ethylene-propylene-trimer rubber manufactured by Mitsui Chemicals, Inc. Meanwhile, 10 parts by weight of a carbon black (spherical carbon) conductive material having a primary particle diameter of 40 nm and a DBP oil absorption of 360 was blended with 90 parts by weight of ethylene-propylene-trimer rubber manufactured by Mitsui Chemicals, and kneaded using two roll mills to prepare rubber containing the conductive material. Subsequently, the rubber containing the conductive material was pressed to produce a square sheet B with a thickness of 0.5 mm and a side length of 200 mm. These rubber molded sheets were heat-pressed at 250°C in the order of sheet A, sheet B, sheet A, sheet B, and sheet A to form five layers, thereby obtaining a laminated sheet with a thickness of 2.5 mm consisting of five layers. When measuring reflection attenuation using this laminated sheet, the reflection attenuation peak with the highest peak attenuation at a peak top frequency of 30 GHz was 12 dB, and the half-width was 2 GHz.
[0113] (Comparative Example 1)
[0114] A single sheet was produced by mixing 4 parts by weight of a spherical carbon conductive material with a primary particle size of 39.5 nm and a DBP oil absorption of 360, used in Reference Example 1, with 96 parts by weight of an ethylene-propylene-trimer rubber manufactured by Mitsui Kagaku Co., Ltd., and kneading using two roll mills to prepare a rubber containing the conductive material, and then pressing the rubber containing the conductive material to form a square sheet with a thickness of 2.5 mm and a side length of 200 mm.
[0115] When measuring the amount of reflection attenuation, compared to Reference Example 1, the frequency band of the peak top of the reflection attenuation peak with the largest amount of attenuation at the peak top was the same as that of Reference Example 1, but the amount of reflection attenuation at the peak top of the reflection attenuation peak was 7dB, and the band was wide with a half-value width of 5GHz, and it was a weak reflection attenuation peak.
[0116] (Reference Example 2)
[0117] 10 parts by weight of the spherical carbon-based conductive material used in Reference Example 1 was mixed with 90 parts by weight of a homopolypropylene resin having a melt flow rate of 30, and the conductive material was fed as a side feed using a twin-screw extruder to produce a conductive master pellet.
[0118] As the resin used for the A layer, a homopolypropylene resin exhibiting a melt flow rate of 30 was used, and as the resin used for the B layer, the above-mentioned conductive master pellet was used. The prepared polypropylene resin and conductive master pellet were each fed into a twin-screw extruder, and melt-kneaded at 270°C in each twin-screw extruder. The mixing conditions in each twin-screw extruder were set such that the screw rotation speed relative to the discharge volume was 0.7. Next, the extruded resin was combined in nine multi-manifold type feed blocks to form an alternating stacked unit with a thickness of 1 mm, consisting of nine layers alternately stacked in the thickness direction with a stacking ratio of 1.0. The obtained alternating stacked unit was configured such that the A layer consists of a total of 5 layers and the B layer containing the conductive material consists of a total of 4 layers, and it was confirmed by transmission electron microscopy that they are alternately stacked in the thickness direction. Furthermore, the layer thickness increased as it approached the center in the thickness direction, and the variation in the thickness of each layer was significant.
[0119] The fabricated alternating laminated units were bonded in pairs with an adhesive sheet of 25 μm thickness interposed, resulting in a laminated sheet with a total of 19 layers including the adhesive layer. When measuring the reflection attenuation, the reflection attenuation peak with the highest peak attenuation was found to have a peak with a peak top frequency of 26 GHz, and the reflection attenuation at the peak top was 16 dB, with a half-width of 2 GHz.
[0120] (Comparative Example 2)
[0121] A conductive master pellet was prepared by including 5 parts by weight of the spherical carbon conductive material used in Reference Example 2 with 95 parts by weight of the homopolypropylene resin having a melt flow rate of 30 used in Reference Example 2, and the conductive master pellet was fed into the twin-screw extruder used in Reference Example 2 as the resins for layer A and layer B, respectively. An alternating stacked unit of layers A and B was prepared under the same conditions as in Reference Example 2, thereby producing a pseudo-single-layer sheet with a thickness of 1 mm (indicated in the table as consisting only of layer A) in which layers A and B are composed of the same material. When the reflection attenuation was measured, the reflection attenuation peak had the largest peak attenuation at a peak top frequency of 65 GHz, the reflection attenuation at the peak top was 11 dB, and the half-width was 10 GHz.
[0122] (Comparative Example 3)
[0123] Two pseudo-single-layer sheets (indicated in the table as consisting only of layer A) prepared in Comparative Example 2 were bonded together with an adhesive sheet having a thickness of 25 μm, thereby forming a laminated sheet with a total of three layers: two pseudo-single-layer sheets and one adhesive layer. When the reflection attenuation was measured, the reflection attenuation peak had the largest peak attenuation with a peak top frequency of 36 GHz, the reflection attenuation of the peak top was 13 dB, and the half-width was 5 GHz.
[0124] (Example 3)
[0125] In Reference Example 2, an alternating stacked unit with a thickness of 1 mm was obtained in the same manner as in Reference Example 2, except that a feed block having 31 slits was used as the feed block and 31 layers were alternately stacked in the thickness direction with a stacking ratio of 1.0. The obtained alternating stacked unit was confirmed by a transmission electron microscope to have 16 layers of A and 15 layers of B containing a conductive material alternately stacked in the thickness direction. In addition, regarding the stacking thickness, compared to the case where the multi-manifold type feed block of Reference Example 2 was used, the coefficient of variation of the layer thickness of B was reduced, but due to the influence of the thixotropic properties of the resin, it became an alternating stacked unit with slight stacking disorder.
[0126] By bonding two fabricated alternating laminated units with an adhesive sheet of 25 μm thickness interposed, a laminated sheet with a total of 63 layers, including the adhesive layer, was obtained. When measuring the reflection attenuation, due to the effect of the increased number of layers, the reflection attenuation at the peak of the peak with the greatest reflection attenuation was 20 dB, and the half-width was 2.1 GHz.
[0127] (Example 4)
[0128] In Example 3, an alternating stacked unit with a thickness of 1 mm was obtained in the same manner as in Example 3, except that a static mixer was inserted in one stage to double the number of layers in the thickness direction after joining from a feed block having 31 layers of slits, thereby increasing the number of layers to 61 layers. It was confirmed by a transmission electron microscope that the obtained alternating stacked unit formed a unit in which A layers were alternately stacked in the thickness direction with 31 layers and B layers with 30 layers. In the part where the 31-layer stacks joined together, the thickness of A layer was doubled. Although the coefficient of variation of the stacking thickness of B layer was approximately the same as in Example 3, it resulted in an alternating stacked unit with stronger stacking disorder than in Example 3.
[0129] By bonding two fabricated alternating laminated units with an adhesive sheet of 25 μm thickness interposed therebetween, a laminated sheet with a total of 123 layers, including the adhesive layer, was obtained. When measuring the reflection attenuation amount, the reflection attenuation amount at the peak top of the reflection attenuation peak, which had the largest attenuation amount at the peak top compared to Example 3, increased to 24 dB.
[0130] (Example 5)
[0131] As the resin constituting layer B, 10 parts by weight of the carbon-based conductive material used in Reference Example 1 were blended with 90 parts by weight of a polyethylene terephthalate resin having a melting point of 254°C and an intrinsic viscosity IV of 0.63, and the mixture was kneaded using a twin-screw extruder in which the conductive material was supplied as a side feed to produce a conductive master pellet. As the resin constituting layer A, a polyethylene terephthalate resin having a melting point of 254°C and an intrinsic viscosity IV of 0.8 was used, and as the resin constituting layer B, the above conductive master pellet was used. The prepared resins were each fed into a twin-screw extruder and melt-kneaded at 280°C in each twin-screw extruder. Next, the extruded resins were combined in a feed block having 31 slits, and a static mixer was interposed as a single stage to form an alternating stacked unit with a thickness of 1 mm, consisting of 61 layers stacked alternately in the thickness direction with a stacking ratio of 1.0. Compared to Example 4, by using a resin that is difficult to exhibit thixotropic properties, an alternating stacked unit with almost no stacking disorder was obtained.
[0132] By bonding two fabricated alternating laminated units with an adhesive sheet of 25 μm thickness interposed therebetween, a laminated sheet with a total of 123 layers, including the adhesive layer, was obtained. When measuring the reflection attenuation amount, it was found that the reflection attenuation peak had the largest attenuation amount at the peak top frequency of 27 GHz, and also that the peak top was steeper than that of Example 4.
[0133] (Example 6)
[0134] In Example 5, a conductive master pellet was used as the resin for layer A by mixing 1 part by weight of the spherical carbon conductive material used in Reference Example 1 with 99 parts by weight of a polyethylene terephthalate resin having a melting point of 254°C and an intrinsic viscosity IV of 0.8, and as the resin for layer B, a conductive master pellet was used by mixing 9 parts by weight of the spherical carbon conductive material with 91 parts by weight of a polyethylene terephthalate resin having a melting point of 254°C and a viscosity IV of 0.63. Except for these differences, a laminated sheet with a total of 123 layers was obtained in the same manner as in Example 5. When the amount of reflection attenuation was measured, since the conductivity of layer A was not very high, it had a reflection attenuation peak with the largest amount of attenuation at the peak top frequency of 26 GHz, and the peak was relatively steep.
[0135] (Example 7)
[0136] In Example 5, a conductive master pellet was used as the resin for layer A by mixing 10 parts by weight of a spherical carbon conductive material having a primary particle size of 8 nm and a DBP oil absorption of 95 mL / 100 g with 90 parts by weight of a polyethylene terephthalate resin having a melting point of 254°C and an intrinsic viscosity IV of 0.8, and as the resin for layer B, a conductive master pellet was used by mixing 5 parts by weight of the spherical carbon conductive material used in Reference Example 1 with 95 parts by weight of a polyethylene terephthalate resin having a melting point of 254°C and a viscosity IV of 0.63. Except for these differences, a laminated sheet with a total of 123 layers was obtained in the same manner as in Example 5. When the reflection attenuation was measured, the reflection attenuation peak had the largest attenuation at the peak top with a peak top frequency of 25 GHz, and the peak had low steepness.
[0137] (Example 8)
[0138] In Example 5, a laminated sheet of 123 layers was obtained using the same resin and manufacturing method as in Example 5, except that the content of the conductive material was 5 parts by weight. As the content was low, conductivity decreased, and the frequency band of the reflection attenuation peak with the largest peak attenuation also shifted to a high frequency band, but steep shielding properties were obtained due to the laminated structure. The laminated sheet had a reflection attenuation peak with the largest peak attenuation at a peak top frequency of 55 GHz, and the reflection attenuation at the peak top of that reflection attenuation peak was 18 dB.
[0139] (Example 9)
[0140] In Example 5, a carbon-based conductive material having a primary particle size of 35 nm and a DBP oil absorption of 500 mL / 100 g was used as the conductive material, and a resin and manufacturing method identical to those in Example 5 were used to obtain a laminated sheet of 123 layers. By changing to a conductive material that further forms a structure, conductivity was improved, while thixotropic properties were strong and the deviation of the laminated thickness increased. The laminated sheet had a reflection attenuation peak with the highest attenuation at the peak top frequency of 11 GHz, and exhibited a high attenuation peak with a reflection attenuation of 25 dB.
[0141] (Example 10)
[0142] In Example 9, a laminated sheet of 123 layers was obtained using the same resin and manufacturing method as in Example 9, except that the amount of conductive material was 3.6 parts by weight. By reducing the amount of conductive material, thixotropy was not produced, no stacking disorder occurred, and a laminated sheet with more aligned layer thickness was obtained. The obtained reflection attenuation peaks were as shown in Table 2.
[0143] (Example 11)
[0144] In Example 5, a carbon-based conductive material having a primary particle size of 44 nm and a DBP oil absorption of 220 mL / 100 g was used as the conductive material, and a resin and manufacturing method identical to those in Example 5 were used to obtain a laminated sheet of 123 layers. The conductive material was difficult to form a structure, and although conductivity was improved by including it in a high concentration, the laminated sheet exhibited strong thixotropic properties due to increased particle concentration and showed lamination disorder. The laminated sheet had a reflection attenuation peak with the largest peak attenuation at the peak top frequency of 38 GHz, a reflection attenuation of 23 dB at the peak top of the reflection attenuation peak, and a laminated sheet having a steep peak with a high RL / fΔ.
[0145] (Comparative Example 4)
[0146] In Example 5, a spherical carbon conductive material having a primary particle size of 8 nm and a DBP oil absorption of 95 mL / 100 g was used as the conductive material, and a total of 123 layers of laminated sheet were obtained in the same manner as in Example 5, except that the amount of the conductive material was 15 parts by weight. The conductive material contained was a carbon material intended to produce jet blackness, and almost no conductivity was obtained within the layers. Furthermore, when the reflection attenuation was measured, the reflection attenuation peak had the largest peak attenuation with a peak top frequency of 48 GHz, the reflection attenuation of the peak top was 4.5 dB, and the half-width was 15 GHz, indicating that the reflection attenuation was small and the material did not exhibit any steepness in the attenuation of electromagnetic waves.
[0147] (Example 12)
[0148] In Example 5, a laminated sheet was obtained by the same manufacturing method as in Example 5, except that the resin used in layer A and the resin used in layer B were reversed to form a 123-layer laminated sheet having a repeating structure of B(AB)n. Since the conductive layer B was placed on the outermost surface, electromagnetic waves were reflected from the surface of the laminated sheet, and the effect of absorption from the inside was weakened. Consequently, the magnitude of the electromagnetic wave reflection attenuation at the peak top, which exhibits the maximum reflection attenuation, was reduced, but the material had a relatively steep peak. In addition, in this example, the layer with lower conductivity is indicated as layer B, and the layer with higher conductivity is indicated as layer A.
[0149] (Example 13)
[0150] In Example 5, 5 parts by weight of the carbon-based conductive material used in Example 5 and 2 parts by weight of a graphene powder material with an average particle size of 5 μm were mixed as the conductive material, and a conductive master pellet was produced by kneading these conductive materials using a twin-screw extruder with side feed. A laminated sheet with a total of 123 layers was obtained using the same resin and manufacturing method as in Example 5, except that the above master pellet was used as the resin for the B layer. By incorporating flat graphene powder, the laminated sheet had significantly improved conductivity in the direction parallel to the sheet surface in the layer containing the graphene powder, and had a reflection attenuation peak with the largest attenuation amount at the peak top with a peak top frequency of 8 GHz, and a reflection attenuation amount at the peak top of the reflection attenuation peak was 36 dB, and was a laminated sheet having a steep reflection attenuation peak with a large RL / fΔ.
[0151] (Example 14)
[0152] As a conductive material, 5 parts by weight of the carbon-based conductive material used in Example 5 and 3 parts by weight of a carbon nanotube material having an average diameter of 1.5 nm and an average length of 500 nm were blended, and a conductive master pellet was produced by side-feeding these conductive materials through twin-screw extruder mixing. A laminated sheet with a total of 123 layers was obtained using the same resin and manufacturing method as in Example 5, except that the above master pellet was used as the resin for the B layer. By using a carbon nanotube material with a high aspect ratio, the laminated sheet was obtained in which the conductivity in the direction parallel to the sheet surface in the layer containing carbon nanotubes was improved, and the reflection attenuation peak with the highest attenuation at the peak top frequency was 6 GHz, the reflection attenuation at the peak top of the reflection attenuation peak was 26 dB, and a laminated sheet having a steep reflection attenuation peak with a large RL / fΔ was obtained.
[0153] (Example 15)
[0154] In Example 13, the fabricated alternating stacked unit was stretched 1.4 times in the long side direction at 90°C and 1.5 times in the width direction at 100°C to obtain a stacked sheet with a thickness of 500 μm. By observing with a transmission electron microscope, a desirable trend was obtained in which the graphene powder was well aligned in a direction parallel to the sheet surface compared to Example 13. The obtained stacked sheet was bonded four sheets together with an adhesive to form the desired stacked sheet. By observing with a transmission electron microscope, a desirable trend was obtained in which both the spherical carbon and graphene powder were well aligned in a direction parallel to the sheet surface. The sheet was designed to be more prone to inducing dielectric polarization and had high damping and steepness compared to Example 13.
[0155] (Example 16)
[0156] In Example 13, an alternating stacking unit was fabricated in the same manner as in Example 13, except that a feed block with 101 slits, in which pressure loss is adjusted by slit length and width, was used as the stacking device and the coefficient of variation of each layer thickness was set to 0.18. The obtained stacked sheets were bonded in two layers with an adhesive interposed to form the target stacked sheet. A stacked sheet was obtained having a reflection attenuation peak with the largest attenuation amount at the peak top, with a peak top frequency of 23 GHz, a reflection attenuation amount at the peak top of the reflection attenuation peak of 30 dB, and a steep reflection attenuation peak with a large RL / fΔ.
[0157] (Example 17)
[0158] In Example 13, an alternating stacking unit was fabricated in the same manner as in Example 13, except that a feed block with 201 slits, in which pressure loss is adjusted by slit length and width, was used as the stacking device. By bonding two fabricated alternating stacking units with an adhesive sheet having a thickness of 25 μm interposed therebetween, a laminated sheet with a total of 403 layers, including the adhesive layer, was obtained. When the thickness of each layer was observed using a transmission electron microscope, it was confirmed that the coefficient of variation of each layer thickness was 0.12. As a laminated sheet, it was a laminated sheet exhibiting the characteristics listed in Table 2.
[0159] (Example 18)
[0160] In Example 13, an alternating stacking unit was fabricated in the same manner as in Example 13, except that a feed block with 501 slits, in which pressure loss is adjusted by slit length and width, was used as the stacking device. By bonding two fabricated alternating stacking units with an adhesive sheet having a thickness of 25 μm interposed therebetween, a laminated sheet with a total of 1003 layers, including the adhesive layer, was obtained. When the thickness of each layer was observed using a transmission electron microscope, it was confirmed that the coefficient of variation of each layer thickness was 0.08. As a laminated sheet, a laminated sheet exhibiting the characteristics listed in Table 2 was obtained.
[0161] (Example 19)
[0162] As a conductive material, 10 parts by weight of graphene powder material with an average particle size of 5 μm, used in Example 13, were mixed, and a conductive master pellet was produced by kneading these conductive materials in a twin-screw extruder with side feed. A laminated sheet of 123 layers was obtained using the same resin and manufacturing method as in Example 13, except that the above master pellet was used as the resin for the B layer. Due to the high conductivity of graphene, a steep peak top was observed at 800 MHz, and a high amount of reflection attenuation was exhibited.
[0163] (Reference Example 20)
[0164] 5 parts by weight of a carbon-based conductive material having a primary particle size of 40 nm and a DBP oil absorption capacity of 400 mL / 100 g was mixed with 95 parts by weight of an isophthalic acid copolymer polybutylene terephthalate resin having a melting point of 210°C, and the conductive material was fed as a side feed using a twin-screw extruder to produce a conductive master pellet.
[0165] As the resin used for the A layer, a polyethylene terephthalate resin having a melting point of 254°C and an intrinsic viscosity IV of 0.8 was used, and as the resin used for the B layer, the above-mentioned conductive master pellet was used. The prepared polyethylene terephthalate resin and conductive resin were each fed into a twin-screw extruder, and melt-kneaded at 270°C in each twin-screw extruder. The mixing condition for each twin-screw extruder was set to a screw rotation speed of 0.7 relative to the discharge volume. Next, the extruded resins were combined in 11 multi-manifold type feed blocks, and a molten sheet with 11 layers alternately stacked in the thickness direction with a stacking ratio of 1.0 was discharged from the die. The discharged molten sheet was cooled and solidified on a cast drum, and by adjusting the drum rotation speed, a laminated sheet with a thickness of 1 mm was obtained. It was confirmed by microscopic observation that the obtained laminated sheet was configured such that the A layer consists of a total of 6 layers and the B layer containing the conductive material consists of a total of 5 layers, and that they are alternately stacked in the thickness direction. The electromagnetic wave attenuation performance of the laminated sheet was as shown in Table 4.
[0166] (Comparative Example 5)
[0167] 2.5 parts by weight of conductive spherical carbon particles having a primary particle size of 40 nm and a DBP oil absorption of 400 mL / 100 g were mixed with 97.5 parts by weight of isophthalic acid copolymer polybutylene terephthalate resin having a melting point of 210°C, and the conductive material was fed as a side feed using a twin-screw extruder to produce a conductive master pellet. The master pellet was extruded from a die to form a sheet, cooled and solidified on a casting drum, and a single-film sheet with a thickness of 1 mm was produced by adjusting the drum rotation speed. The performance of the obtained single-film sheet is shown in Table 3, and no significant electromagnetic shielding performance exceeding the volume law was obtained.
[0168] (Comparative Example 6)
[0169] In Comparative Example 5, a single-layer sheet with a thickness of 0.5 mm was obtained by increasing the drum rotation speed. By bonding two of these single-layer sheets with an acrylic adhesive sheet with a thickness of 0.05 mm, a three-layer laminated sheet having a layer containing conductive particles on the outermost layer was obtained (indicated in the table as consisting only of layer A). The performance of the obtained single-layer sheet is as shown in Table 3, and sufficient electromagnetic shielding performance exceeding the volume law was not obtained in the three-layer laminate.
[0170] (Example 21)
[0171] In Reference Example 20, two types of resins were combined in a feed block having 51 slits, and a molten sheet with 51 layers alternately stacked in the thickness direction with a stacking ratio of 1.0 was extruded from a die. Except for this, a laminated sheet with a thickness of 1 mm was obtained in the same manner as in Reference Example 20. Microscopic observation confirmed that the obtained laminated sheet was configured such that A layers consisted of a total of 26 layers and B layers containing a conductive material consisted of a total of 25 layers, and were alternately stacked in the thickness direction. As shown in Table 4, by increasing the number of layers and using a slit-type feed block, a result was obtained in which the amount of reflection attenuation at the reflection attenuation peak was improved.
[0172] (Example 22)
[0173] In Reference Example 20, two types of resins were combined in a feed block having 101 slits, and a molten sheet with 101 layers alternately stacked in the thickness direction with a stacking ratio of 1.0 was extruded from a die. Except for this, a laminated sheet with a thickness of 1 mm was obtained in the same manner as in Reference Example 20. Microscopic observation confirmed that the obtained laminated sheet was configured such that layer A consists of a total of 51 layers and layer B containing a conductive material consists of a total of 50 layers, and that they are alternately stacked in the thickness direction. As shown in Table 4, by further increasing the number of layers, a result was obtained in which the amount of reflection attenuation at the reflection attenuation peak was further improved.
[0174] (Example 23)
[0175] In Example 22, the drum rotation speed was increased to obtain an alternating laminated unit with a thickness of 0.33 mm. By bonding three of these alternating laminated units with an acrylic adhesive sheet with a thickness of 0.05 mm, a laminated sheet with a total of 305 layers and a thickness of approximately 1.0 mm was obtained. The performance of the obtained laminated sheet is shown in Table 4, and the effect of increasing the number of layers was obtained.
[0176] (Example 24)
[0177] In Reference Example 20, two types of resins were combined in a feed block having 301 slits, and a molten sheet with 301 layers alternately stacked in the thickness direction with a stacking ratio of 1.0 was extruded from a die. Except for this, a laminated sheet with a thickness of 1 mm was obtained in the same manner as in Reference Example 20. Microscopic observation confirmed that the obtained laminated sheet was configured such that layer A had a total of 151 layers and layer B containing a conductive material had a total of 150 layers, and that they were alternately stacked in the thickness direction. Compared to Example 23, by using a slit-type feed block with a larger number of layers, the non-uniformity of the layer thickness was reduced, and a laminated sheet exhibiting more severe electromagnetic shielding properties was obtained.
[0178] (Example 25)
[0179] In Example 22, the drum rotation speed was increased to obtain a laminated sheet with a thickness of 0.5 mm. By thinning, as described in Table 4, a laminated sheet was obtained in which the frequency band of the reflection attenuation peak with the largest attenuation at the peak top was shifted to a high frequency while maintaining the magnitude of the reflection attenuation amount compared to the laminated sheet of Example 22.
[0180] (Example 26)
[0181] A conductive master pellet was produced by mixing 10 parts by weight of a carbon-based conductive material used in Example 11, which has a primary particle size of 44 nm and a DBP oil absorption capacity of 220 mL / 100 g, with 90 parts by weight of an isophthalic acid copolymer polybutylene terephthalate resin having a melting point of 210°C, and then kneading using a twin-screw extruder in which the conductive material is supplied as a side feed.
[0182] As the resin used for the A layer, a polyethylene terephthalate resin having a melting point of 254°C and a viscosity IV of 0.8 was used, and as the resin used for the B layer, the above-mentioned conductive master pellet was used. The two types of resins were combined in a feed block having 101 slits identical to those in Example 22, and a molten sheet with 101 layers alternately stacked in the thickness direction with a stacking ratio of 1.0 was extruded from a die. The extruded molten sheet was cooled and solidified on a cast drum, and by adjusting the drum rotation speed, a laminated sheet with a thickness of 1 mm was obtained. By adding a high concentration of a material with low conductivity, a laminated sheet exhibiting good electromagnetic wave cutting properties in the high-frequency band was obtained as described in Table 4.
[0183] (Example 27)
[0184] In Example 26, barium titanate, a dielectric material, was used as a dielectric constant modifier for the conductive master pellet. Specifically, 10 parts by weight of a carbon-based conductive material having a primary particle size of 44 nm and a DBP oil absorption of 220 mL / 100 g and 20 parts by weight of barium titanate from Sakai Kagaku Kogyo Co., Ltd., having an average particle size of 0.5 μm, were blended with 80 parts by weight of isophthalic acid copolymer polybutylene terephthalate resin having a melting point of 210°C to form the conductive master pellet. Except for this, the process was the same as in Example 26 to obtain a laminated sheet with a thickness of 1 mm. As shown in Table 4, by adjusting the dielectric constant, a laminated sheet with superior electromagnetic shielding properties could be obtained.
[0185] (Example 28)
[0186] A conductive master pellet was produced by mixing 5 parts by weight of a carbon-based conductive material used in Example 9, which has a primary particle size of 35 nm and a DBP oil absorption capacity of 500 mL / 100 g, with 95 parts by weight of an isophthalic acid copolymer polybutylene terephthalate resin having a melting point of 210°C, and then kneading using a twin-screw extruder in which the conductive material is supplied as a side feed.
[0187] As the resin used for the A layer, a polyethylene terephthalate resin having a melting point of 254°C and a viscosity IV of 0.8 was used, and as the resin used for the B layer, the conductive master pellet was used. The two types of resins were combined in a feed block having 101 slits identical to those in Example 22, and a molten sheet with 101 layers alternately stacked in the thickness direction with a stacking ratio of 1.0 was extruded from a die. The extruded molten sheet was cooled and solidified on a cast drum, and by adjusting the drum rotation speed, a laminated sheet with a thickness of 1 mm was obtained. As shown in Table 5, although the material had a high imaginary part of the dielectric constant, a laminated sheet exhibiting high electromagnetic shielding properties was obtained.
[0188] (Example 29)
[0189] In Example 28, barium titanate, a dielectric material, was used as a dielectric constant modifier for the conductive master pellet. Specifically, 5 parts by weight of a carbon-based conductive material having a primary particle size of 35 nm and a DBP oil absorption of 500 mL / 100 g and 20 parts by weight of barium titanate from Sakai Kagaku Kogyo Co., Ltd. with an average particle size of 0.5 μm were blended with 85 parts by weight of isophthalic acid copolymer polybutylene terephthalate resin having a melting point of 210°C, to form the conductive master pellet. Except for this, the process was the same as in Example 28 to obtain a laminated sheet with a thickness of 1 mm. As shown in Table 5, by adjusting the dielectric constant, a laminated sheet with excellent electromagnetic shielding properties could be obtained.
[0190] (Example 30)
[0191] In Example 28, as a dielectric constant modifier for the conductive master pellet, a graphene powder material with an average particle size of 5 μm, which was used in Example 13 as another carbon-based conductive material, was used. Specifically, a conductive master pellet was prepared by mixing 2 parts by weight of a carbon-based conductive material having a primary particle size of 35 nm and a DBP oil absorption of 500 mL / 100 g with 95 parts by weight of an isophthalic acid copolymer polybutylene terephthalate resin with a melting point of 210°C, and 3 parts by weight of the graphene powder material with an average particle size of 5 μm. Except for this, a laminated sheet with a thickness of 1 mm was obtained in the same manner as in Example 28. As shown in Table 5, by adjusting the dielectric constant, a laminated sheet exhibiting superior electromagnetic shielding properties compared to Example 28 was obtained.
[0192] (Example 31)
[0193] In Example 22, a laminated sheet with a thickness of 1 mm was obtained in the same manner as in Example 22, except that a 6-nylon resin having a melting point of 222°C was used as the resin for the A layer. By using a resin with a high dielectric constant as the raw material constituting the A layer, the amount of reflection attenuation was reduced to some extent, as shown in Table 5. It is thought that the balance of dielectric constants between the A layer and the B layer was not to the extent of Example 22.
[0194] (Example 32)
[0195] In Example 22, a laminated sheet with a thickness of 1 mm was obtained in the same manner as in Example 22, except that a conductive master pellet was used in which 2 parts by weight of a carbon-based conductive material having a primary particle size of 35 nm and a DBP oil absorption of 500 mL / 100 g, used in Example 9, was blended with a polyethylene terephthalate resin having a melting point of 254°C and a viscosity IV of 0.65 as the resin used on the A-layer side. As shown in Table 5, in addition to the reduction in attenuation as in Example 31, a result was obtained in which the frequency band of the reflection attenuation peak, which has the largest attenuation at the peak top, shifted toward the high frequency side.
[0196] (Example 33)
[0197] In Example 22, the obtained molten sheet was cooled and solidified in a cast drum, and then stretched twice in the conveying direction of the sheet using a roll group adjusted to a temperature of 85°C due to the difference in peripheral speed of the rolls to obtain a stretched laminated sheet with a thickness of 0.5 mm. By undergoing the stretching process, the dielectric constant was improved due to the effect of the carbon-based conductive material added to the B layer being dispersed and oriented in the plane direction, and a laminated sheet having the properties shown in Table 5 was obtained.
[0198] (Example 34)
[0199] In Example 22, the obtained molten sheet was cooled and solidified in a cast drum, then stretched three times in the conveying direction of the sheet by the difference in peripheral speed of the rolls using a roll group adjusted to a temperature of 85°C, and then rapidly cooled. Subsequently, the sheet stretched in the conveying direction was guided to a tenter, and the sheet was conveyed while gripping both ends with clips, and stretched 3.3 times in the width direction in a room controlled at 120°C to obtain an alternating laminated unit with a thickness of 0.166 mm. The obtained alternating laminated unit was bonded three sheets with an acrylic adhesive sheet with a thickness of 0.025 mm interposed therebetween to obtain a laminated sheet with a total of 305 layers and a thickness of approximately 0.5 mm. The properties of the obtained laminated sheet are as described in Table 5, and it was possible to obtain a laminated sheet having excellent electromagnetic shielding properties that exceed the volume law.
[0200] (Example 35)
[0201] By subjecting the molten sheet obtained in Example 30 to the stretching process described in Example 34, an alternating laminated sheet with a thickness of 0.166 mm was obtained. By bonding three of the obtained alternating laminated units with an acrylic adhesive sheet with a thickness of 0.025 mm interposed therebetween, a laminated sheet with a total of 305 layers and a thickness of approximately 0.5 mm was obtained. Due to the effect of the dispersion arrangement of flat carbon within the plane, a laminated sheet with excellent electromagnetic shielding properties that transcend the concept of the volume law was obtained, just like in Example 34.
[0202]
[0203]
[0204]
[0205]
[0206]
[0207] Industrial Applicability
[0208] The laminated sheet of the present invention comprises a unit in which a layer of high conductivity and a layer of low conductivity are alternately laminated, thereby enabling the achievement of a high electromagnetic wave attenuation amount while maintaining a thin film containing a low concentration of conductive material, which was difficult to achieve with conventional single-film or low-layer sheets. In a preferred embodiment, since only electromagnetic waves of a specific frequency can be rapidly and strongly shielded, it is possible to prevent malfunctions in devices using electromagnetic waves in a similar frequency band or to prevent information leakage in high-capacity information communication caused by high-frequency electromagnetic waves. Specifically, it can be suitably utilized in electronic devices or communication devices using communication technology that uses electromagnetic waves in the GHz frequency band, or in vehicles used as means of transportation equipped with such devices, or in transportation vehicles including all infrastructure for traffic control. Explanation of the symbols
[0209] 1: Reflection attenuation peak 2: Reflection attenuation at the peak top at the reflection attenuation peak with the greatest peak attenuation (Reflection attenuation RL) 3: Half width of the reflection attenuation peak with the greatest attenuation at the peak top
Claims
Claim 1 A laminated sheet comprising an alternating laminated unit in which a total of five or more layers are alternately laminated, wherein two layers with different conductivity are referred to as Layer A for convenience and Layer B for higher conductivity, wherein only Layer B contains a conductive material and Layer B has higher conductivity than Layer A, wherein, for the laminated sheet, when a frequency-reflection attenuation curve is obtained with the vertical axis representing reflection attenuation and the horizontal axis representing frequency, the reflection attenuation at the peak of the reflection attenuation peak with the largest reflection attenuation at the peak (reflection attenuation RL) is 5.0 dB or more, the number of interfaces per unit thickness between Layer A and Layer B is 2 surfaces / 100 µm or more, and the surface resistance of Layer B is 1.0 × 10⁻⁶ 5 A laminated sheet characterized by being less than [Ω / □], wherein the real part εh'[-] and the imaginary part εh"[-]] of the complex permittivity of the B layer satisfy the following equation (A) or (B). (A) εh"≥1, and also 0.17εh'+2.3≤εh"≤0.27εh'+3.3 (B) 5≥εh"≥1, and also 0.02εh'+1≤εh"≤0.07εh'+1.9 Claim 2 A laminated sheet according to claim 1, wherein RL [dB] is the reflection attenuation at the peak top of the reflection attenuation peak with the largest reflection attenuation at the peak top, f [GHz] is the frequency corresponding to the peak top, and t [mm] is the thickness of the laminated sheet, and RL / (t×f) is 0.2 or more and 15 or less. Claim 3 A laminated sheet according to claim 1 or 2, wherein the reflection attenuation peak with the largest attenuation amount of the peak top exists in a frequency band of 1 to 100 GHz. Claim 4 In claim 1 or 2, the surface resistance value of the outermost surface of at least one side of the laminated sheet is 1.0 × 10 5 [Ω / □] or greater, laminated sheet. Claim 5 A laminated sheet according to claim 1, wherein the coefficient of variation tBσ / tB is 0.3 or less when the average value of the layer thickness of the B layer is tB[mm] and the standard deviation is tBσ[mm]. Claim 6 A laminated sheet according to claim 1, wherein the conductive material is a material having carbon as its main component. Claim 7 A laminated sheet according to claim 6, wherein the material having carbon as a main component is carbon black. Claim 8 A laminated sheet according to claim 7, wherein the dibutyl phthalate (DBP) oil absorption capacity of the carbon black is 150 [mL / 100g] or more. Claim 9 A laminated sheet according to claim 7, comprising, in addition to the carbon black, a conductive material other than spherical carbon. Claim 10 A laminated sheet according to claim 1, wherein the conductive material is included in an amount of 1% or more and less than 15% by weight relative to the total weight of the laminated sheet. Claim 11 A laminated sheet according to claim 1 or 2, wherein layer A and layer B are both composed mainly of thermoplastic resin. Claim 12 A laminated sheet according to claim 1 or 2, wherein the ratio RL / fΔ of the half-width fΔ[GHz] of the reflection attenuation peak with the largest electromagnetic wave attenuation at the peak top and the electromagnetic wave attenuation (maximum attenuation) RL[dB] of the reflection attenuation peak with the largest electromagnetic wave attenuation at the peak top is 5.0 or greater. Claim 13 An electromagnetic shield having a laminated sheet as described in paragraph 1 or 2 and a reflector. Claim 14 An electromagnetic wave-related device corresponding to any of the devices used in electronic devices, communication devices, and transportation vehicles, characterized by having at least one of a laminated sheet described in claim 1 or 2 and an electromagnetic shield having said laminated sheet and a reflector. Claim 15 delete Claim 16 delete Claim 17 delete
Citation Information
Patent Citations
Electromagnetic wave absorber
JP2019057730A
Electromagnetic wave absorber
KR1020180093889A
Electronic wave absorber
JP2000059066A
Electromagnetic wave absorption sheet, lamination thereof, and electromagnetic wave absorptivity housing using these
JP2006114877A
